Latitudinal mixing and movement of eastern school whiting (Sillago flindersi) in south-eastern Australia indicated from otolith trace element chemistry - Karina C. Hall; Kris Cooling; Brendan P. Kelaher; Kyne Krusic-Golub; Stephen G. Morris; Curtis Champion; Renaud Joannes-Boyau (Estuarine, Coastal and Shelf Science, 2026)

Contributions of wind-sea and ocean swell to hurricane-generated surface waves on the continental shelf offshore of Nova Scotia in Atlantic Canada - Sarah E. Hall; Ryan P. Mulligan; Barret L. Kurylyk (Continental Shelf Research, 2026)

Corrigendum to “Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales” [Environ. Res. (2026) 124912] - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Corrigendum to “Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales” [Environ. Res. (2026) 124912] - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David C. Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Quantifying soybean biological nitrogen fixation using long-term isotope enrichment - Ophelia Tsai; Steven J. Hall; George L. Graef; Luis G. Posadas; James E. Specht; William G. Crumpton; Matthew J. Helmers; Shawn P. Conley (Plant and Soil, 2026)
Background and aims Biological nitrogen fixation (BNF) supplies much of soybean ( Glycine max (L.) Merr.) nitrogen (N) demand, but reported fixation rates vary widely, leading to uncertainty in the soybean N cycle. We quantified whole-plant soybean BNF and N allocation using long-term 15 N labeling to assess whether BNF can offset grain N removal in a high-yielding system, and to quantify root contributions to fixed N. Methods Field mesocosms in Iowa, USA received three legacy fertilizer N rates as 2 atom% 15 N-enriched urea for four prior seasons of maize ( Zea mays L.) production. In 2024, N-fixing and non-N-fixing soybeans were grown to physiological maturity. Grain, aboveground biomass, and roots were analyzed to quantify BNF and to estimate whole-plant N budget. Results Soybean derived 81.8% ± 1% (SE) of total plant N from BNF. Legacy N rate had no effect on whole-plant N accumulation, BNF, or N partitioning among tissues (p > 0.05). Roots contained ~2% of total fixed N, with most BNF-derived N allocated to grain. High grain N removal was largely offset by BNF (174.7 ± 8.9 kg N ha −1 ), resulting in a near-neutral partial N balance (−5.7 ± 2 kg N ha⁻ 1 ). Conclusion From this one-season mesocosm study, our finding of negligible fixed N in soybean roots indicates that neglecting root BNF does not necessarily bias conclusions about soybean N cycle. However, the combination of long-term isotope labeling and non-nodulating isolines yielded much less variable and higher BNF rates than previous studies, suggesting the possibility of underestimation for soybean BNF in historical studies.

Recompression Improves Release Success in Pollack ( Pollachius pollachius ): A Step Towards Assessing Post Release Mortality in a Recreational Fishery - T. Stamp; R. Mawer; R. Conlon; A. E. Hall; P. Davies; R. Nesbit; D. Uren; T. Morris; S. Sullivan; S. Thomas; B. D. Stewart; H. Rudd; et al. (Fisheries Management and Ecology, 2026)
The recreational fishery for pollack ( Pollachius pollachius ) in the northeast Atlantic is impacted by the species' high sensitivity to barotrauma. When captured at depth and brought to the surface, gas expansion within the peritoneal cavity can cause a variety of injuries and hinder release. Via an experimental weighted cage, this study evaluated the efficacy of releasing Pollack at depth as a barotrauma mitigation strategy. We found that depth‐release significantly increased the probability of released Pollack displaying an active escape response to 83%, compared to 56% for surface‐released fish; however, increased capture depth and fish size negatively affected success. Camera observations of depth‐released Pollack confirmed the recovery of vital reflexes (vestibulo‐ocular reflex, equilibrium maintenance) within 1.5–4 min. Further acoustic telemetry demonstrated that individuals subsequently displayed active dispersion from the release site (0.1–23.8 km) and showed active vertical movements for up to 6 months post‐release. These findings indicate that depth‐release improves survival outcomes, though further research is required to optimise release methods in open‐water environments.

Post‐Release Mortality of European Bass ( Dicentrarchus labrax ) Discarded From Small‐Scale Estuarine Fishing - J. E. Stewart; T. Stamp; P. Davies; A. Hall; T. Robbins; L. Stewart; E. V. Sheehan (Fisheries Management and Ecology, 2026)
Estuaries provide essential habitats for many fish species, but their confined and accessible nature may increase fish vulnerability to capture, and few empirical studies have quantified the value of restricting net fisheries in such areas. Furthermore, management measures for some fisheries promote discarding (e.g., of European sea bass; Dicentrarchus labrax ), yet the mortality of fish discarded from small‐scale inshore fisheries is poorly understood. We used condition assessments, Reflex Action Mortality Predictor scores and acoustic tracking to evaluate post‐release mortality of bass captured in small‐scale estuarine netting and angling. Gillnet‐caught bass exhibited a range of stress responses and 20%–24% mortality shortly after capture, whereas angler‐caught bass showed no short‐term post‐release mortality. Six‐month survival of fish released in good condition was > 80% for both gear types. However, strong site fidelity and residency were observed which could increase recapture risk. Our findings underscore the potential benefits of prohibitions of netting in sensitive estuaries and can inform fisheries discards management.

Prioritizing chemicals for developmental neurotoxicity by integrating data from a new approach methods (NAMs) battery covering key cellular events in neurodevelopment - Laura A. Hall; Jui-Hua Hsieh; Skylar W. Marvel; Mamta Behl; Ellen Fritsche; Katharina Koch; Anna Kreutz; Marcel Leist; Arantza Muriana; Timothy J. Shafer; Jason P. Stanko; Robert C. Sills; et al. (NeuroToxicology, 2026)

Bee-ing similar: low diversity, no population structure, and signals of adaptation in two North Dakota bumble bees - Rhiannon Hall; Meggan A. Alston; Jason P. Harmon; Clint R. V. Otto; Travis Seaborn (Biodiversity and Conservation, 2026)
Habitat fragmentation and destruction are driving widespread declines in ecosystem function, species abundance, and genetic diversity across the globe. Among the affected taxa are bumble bees (genus Bombus ), which are essential pollinators. Bumble bee declines have been linked to anthropogenic pressures such as land-use change and climate change. To better understand how the environment is shaping bumble bee populations, we employed a landscape genetics approach to examine the genetic diversity, population structure, and potential local adaptation of two widespread species— Bombus ternarius and Bombus griseocollis —across North Dakota. From 2017–2020, 161 B. ternarius and 200 B. griseocollis bumble bees were sampled in ND across 13 and 17 sites, respectively. We found low levels of heterozygosity and inbreeding across all populations for both species, with no evidence of population structure or isolation by distance. Our results revealed signatures of potential local adaptation to climatic variables and land cover characteristics, suggesting that our species are adapted to environmental gradients across the state. Having similar results between both species across all analyses suggests that other wide-ranging bumble bees in the region may share these patterns. High connectivity can buffer short-term population losses, but low genetic diversity may constrain adaptive potential and reduce resilience to future environmental change and emerging threats. Our findings have broad applicability to other pollinators and taxa facing similar environmental pressures. Both species have populations that continually exchange genes creating widespread connectivity but are still locally shaped by adaptation.

High-resolution MRI evidence for age- and sex-related changes in hippocampal subfield volume during healthy aging - Megan C. Hall; Giorgia Picci; Maggie P. Rempe; Jason A. John; Lauren K. Webert; Kellen M. McDonald; Hannah J. Okelberry; Hallie J. Johnson; Lucy K. Horne; Madelyn P. Willett; Ryan J. Glesinger; Danielle L. Rice; et al. (GeroScience, 2026)

Genome-wide association analysis of reproductive partitioning traits in a genetically diverse elite spring wheat panel - Aleyda Sierra-Gonzalez; Matthew P. Reynolds; Gemma Molero; Ryan Joynson; Anthony Hall; M. John Foulkes (Euphytica, 2026)

Using Bayesian methods to evaluate the diagnostic performance of blood-based diagnostic tests for American cutaneous leishmaniasis and Chagas disease in rural Panamanian dogs in the absence of a gold standard - Kimberly Archbold; Vanessa Pineda; José E. Calzada; Azael Saldaña; Adelys Reina; Alberto Cumbrera; Ayesha Rodríguez; Chystrie Rigg; Caleb Hawkins; Daniel Mendieta; John P. Schmidt; Julie Velásquez Runk; et al. (Veterinary Parasitology, 2026)

Forest restoration thinning and burning treatments create habitat mosaics and facilitate succession of grasshopper and cricket communities (Orthoptera) - Robert R. Parmenter; Tyler J. Obermeit; Benjamin P. Stout; Sarah M. Hall; Orrin B. Myers; David C. Lightfoot (Forest Ecology and Management, 2026)

Development of a New Aerosol Delivery System for Administering Aerosol Surfactant Therapy to Preterm Infants Through a Laryngeal Mask Airway - Sarah C. Strickler; Caleb J. Dalton; Felicia G. Hall; Dale R. Farkas; Mohammad A. M. Momin; Robert M. DiBlasi; Michael Hindle; P. Worth Longest (AAPS PharmSciTech, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Barcoding‐Inferred Biodiversity of Shallow‐Water Indo‐Pacific Demosponges - Dirk Erpenbeck; Adrian Galitz; Michael L. Berumen; Gabriele Büttner; Cécile Debitus; Moritz Dirnberger; Merrick Ekins; Kathryn Hall; Leonard Namuth; Sylvain Petek; Neda Rahnamae; Maggie M. Reddy; et al. (Journal of Biogeography, 2026)
Aim The Indo‐Pacific is the world's largest marine biogeographic region. It is characterised by different degrees of connectivity among its subregions and harbours the majority of demosponge species currently known to science. Comparisons between regional sponge faunas have been undertaken in the past, mostly based on morphological species identification. The Sponge Barcoding Project, in tandem with regional DNA taxonomy campaigns, provides one of the largest DNA‐based taxonomic data collections from sponges of the Indo‐Pacific. Here, we utilise the barcoding data in the most extensive molecular biodiversity study of sponges to date, which reveals patterns of shallow‐water demosponge faunal connectivity, endemism and distribution in the Indo‐Pacific with a level of resolution unavailable in prior morphology‐based studies. Location Demosponge specimens in this study cover 13 marine provinces (MPs) of the Indo‐Pacific. Methods We classified demosponge barcodes from 1910 sponge samples into 701 molecular operational taxonomic units (MOTUs) using 28S rRNA. MOTU composition of the MPs was compared based on Jaccard and Sørenson dissimilarities and other biodiversity indices. Results Our data corroborated high endemism in MPs (up to 84.1% endemic MOTUs). Faunal overlaps are between the Red Sea and the Gulf, which displayed small connectivity with other MPs in the Western Indian Ocean. The Western Indian Ocean is a strong faunistic boundary to the Central Indo‐Pacific, to which the Polynesian sponge faunas were comparatively isolated as well. Main Conclusions Our data corroborate case studies on sponges that generally reject the presence of cosmopolitan or otherwise widespread sponge species, instead revealing high levels of regional endemism. This is consistent with similar observations and hypotheses in other marine invertebrates, and highlights the need for close regional monitoring to identify biodiversity changes. Connectivity among Indo‐Pacific MPs differs for demosponges in many aspects from that of other marine taxa, hypothetically due to their shorter pelagic larval phase.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A history of the collaborative group of the Americas on inherited gastrointestinal cancer (CGA-IGC): 1995–2025 - Beth Dudley; Bruce M. Boman; Marc S. Greenblatt; Steven H. Erdman; Paul E. Wise; Randall E. Brand; Carol A. Burke; Jose G. Guillem; Michael J. Hall; Heather Hampel; Brandie Heald; Matthew F. Kalady; et al. (Familial Cancer, 2026)

Linking persistent open-vent activity and caldera-forming eruptions at Tofua volcano, Tonga - Chris W. Firth; Shane J. Cronin; John T. Caulfield; Simon P. Turner; Adinda Peyra; James B. Garvin; Taaniela Kula; Annahlise Hall (Bulletin of Volcanology, 2026)
Tofua volcano (Tonga) currently exhibits persistent, open-vent activity; however, this contrasts with previous explosive, caldera-forming eruptions. To understand the relationship between these dichotomous eruption styles, we present new field observations and satellite remote sensing data that reveal excess degassing of SO 2 and demonstrate significant magma accumulation over timescales of centuries. Current activity takes the form of open-vent behaviour, with a small, active lava lake and persistent gas and heat emissions. Heat flux, determined by the Moderate Resolution Imaging Spectroradiometer, averages 6.9 MW and has been both persistent over 24 years and consistent in magnitude. SO 2 flux measured by in situ UV spectrometry in October 2022 averaged 8.1 kg/s. Satellite and aerial imagery reveal no change to the volcano’s morphology and negligible eruption of lava since at least 1968. Patchy historical reports suggest activity like this has continued for 200 years or more. The observed gas flux requires magma supply rates of 6.1 × 10 4 m 3 /day. These are clearly not matched by eruption rates, implying an excess degassing process with magma accumulating rapidly beneath the volcano. The history of this volcano suggests that such accumulated magma may be tapped on intervals as short as ~ 450 years to produce large-volume (5–10 km 3 ), caldera-forming eruptions. This is consistent with tephra records which show that two or possibly three large caldera-forming eruptions have occurred in the last 1.3 ka. This process is corroborated by 226 Ra isotope evidence, which shows that caldera-forming ignimbrites tapped magmas that were stored for 1–2 kyr longer than those feeding post-caldera lavas.

Extraordinary claims require extraordinary evidence: evaluating nodule-associated dark oxygen production - Patrick Downes; Angel Cuesta; Alden Denny; Anders Tengberg; Per O. J. Hall; Lars-Kristian Trellevik; Werner Svellingen; Marcel Jaspars; Alexander P. Webber; Felipe Sales de Freitas; Joaquim P. Bento; Leigh Marsh; et al. (Frontiers in Marine Science, 2025)

The NASA VIIRS burned area product, global validation, and intercomparison with the NASA MODIS burned area product - Louis Giglio; Luigi Boschetti; David P. Roy; Joanne V. Hall; Maria Zubkova; Michael Humber; Haiyan Huang; Vladyslav Oles (Remote Sensing of Environment, 2025)

Strontium isotopes and Rb/Sr tracers in surface soils for locating subsurface lithium pegmatites - Grace A. Hall; Gordon D.Z. Williams; Mona-Liza C. Sirbescu; P. Louis Lu; Gary S. Dwyer; Daniel D. Richter; Avner Vengosh (Applied Geochemistry, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Experimental Immigration Mediates Ecological Selection and Drift in Monarch Microbiome Assembly - Christopher P. Catano; James G. DuBose; Lydia Fuller‐Hall; Joselyne Chavez; Jacobus C. de Roode (Ecology Letters, 2025)
The distribution of biodiversity depends on processes operating across scales, yet multiscale paradigms have struggled to permeate host‐microbiome research. Instead, host‐microbiome research has focused on host selection and has struggled to explain the high variation in microbial composition across individuals. By integrating multi‐scale ecological theory with experimental manipulation of bacteria colonizing monarch butterfly caterpillars, we test the hypothesis that immigration from the regional species pool alters the importance of niche selection and drift in causing variation in gut bacterial communities across individuals and through ontogeny. Higher immigration increased the dominance of certain bacteria, causing greater convergence in bacterial composition across the caterpillar life stage. Conversely, limited immigration made colonization more stochastic, resulting in more unpredictable variability in bacterial composition across individuals. Our study reveals that immigration mediates the balance between host selection and drift, demonstrating that processes operating at scales beyond the individual are underappreciated but critical for structuring host‐microbiome symbioses.

What’s going on in the livers in my study? Test-item related toxicity or spontaneous finding? - M. Rezaee; P. Hall; S. Rombouts; F. Poosti; L. Ratsamy; J. Ling; R. Fleurance (Journal of Comparative Pathology, 2025)

Histopathological and immunohistochemical characterisation of inflammatory lesions in flying foxes naturally infected with Australian Bat Lyssavirus (ABLV). - Y. Lin Tan; M. Gimeno; P. Pinczowski; S. Gestier; E. Hall; M. Krockenberger (Journal of Comparative Pathology, 2025)

Mollusc epifaunal assemblages are simplified due to habitat shifts under ocean acidification - Gustavo M. Martins; Javier Herrero; Cristina Canella; Sérgio P. Ávila; Afonso Prestes; Joana Barcelos e Ramos; Jason M. Hall-Spencer; João Faria (Estuarine, Coastal and Shelf Science, 2025)

The influence of biochar pyrolysis temperature on anaerobic digestion of chicken litter in a leach bed coupled to a biochar filter - Ben A. Collins; Cristian H. Birzer; Stephen P. Kidd; Tony Hall; Paul R. Medwell (Bioresource Technology Reports, 2025)

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Lithium toxicity to marine organisms: Establishing water quality guideline values to protect temperate and tropical marine life - Scott J. Markich; Jeremy P. Hall; Jude M. Dorsman; Paul L. Brown (Chemosphere, 2025)

Otolith oxygen isotopes inform dispersal and movement patterns for eastern school (Sillago flindersi) and stout (Sillago robusta) whiting along the east coast of Australia - Melissa Tan; Brendan P. Kelaher; Lewis Adler; Curtis Champion; Karina C. Hall (Fisheries Research, 2025)

Understanding the effects of geotechnical properties on viscous erosion rate from plume surface interactions - B. Dotson; A. St John; R. Hall; D. Sapkota; D. Britt; P. Metzger (Planetary and Space Science, 2025)

Prenatal PFAS exposures and cardiometabolic health in middle childhood in the MIREC cohort - Alan J. Fossa; Amber M. Hall; George D. Papandonatos; Tye E. Arbuckle; Jillian Ashley-Martin; Michael M. Borghese; Jenny Bruin; Aimin Chen; Mandy Fisher; John E. Krzeczkowski; Bruce P. Lanphear; Amanda J. MacFarlane; et al. (Environmental Research, 2025)

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Strategic Plan of the Collaborative Group of the Americas on Inherited Gastrointestinal Cancer (CGA-IGC): A practical roadmap to move the hereditary gastrointestinal cancer field forward - Bryson W. Katona; Peter P. Stanich; Anu Chittenden; Michael J. Hall; Gregory E. Idos; Cathryn Koptiuch; Alicia Latham; Rachel Pearlman; Aparajita Singh; Elana Levinson; Beth Dudley (Familial Cancer, 2025)

Effects of training paradigm on dogs’ (Canis familiaris) acquisition and generalization of odors when trained with multiple explosives classes - S.A. Kane; G.N. Cupp; B. Rogers; D. Copeland; C. Collins-Pisano; J. Davis-Miller; L. Lazarowski; P. Waggoner; E.O. Aviles-Rosa; J. Denapoli; P.A. Prada-Tiedemann; N.J. Hall (Applied Animal Behaviour Science, 2025)

Evaluation of BRCA1/2 testing rates in epithelial ovarian cancer patients: lessons learned from real-world clinical data - Lieke Lanjouw; Claire J. H. Kramer; Arja ter Elst; Geertruida H. de Bock; Katja N. Gaarenstroom; Refika Yigit; Lieke P. V. Berger; Christi J. van Asperen; Sabrina Z. Commandeur-Jan; Dimas M. X. van der Hall; Mathilde Jalving; Marjolein J. Kagie; et al. (Familial Cancer, 2025)
Identification of somatic and germline BRCA1/2 pathogenic variants in epithelial ovarian cancer (EOC) patients is essential for determining poly-(ADP-ribose)-polymerase (PARP) inhibitor sensitivity and genetic predisposition. In the Netherlands, BRCA1/2 testing changed to a tumor-first approach to efficiently identify both somatic and germline pathogenic variants in all patients. Here, we performed an in-depth evaluation of the first four years of the tumor-first test-pathway. Data of consecutive series of patients diagnosed with EOC in two regions were obtained from the Netherlands Cancer Registry. Tumor and/or germline test data were retrieved from hospital databases. The primary outcome was the percentage of patients completing the BRCA1/2 test-pathway, defined as having a negative tumor test or a referral for a germline test in case of a positive tumor test or no tumor test. Factors associated with test-pathway completion were identified through multivariable logistic regression analysis. In total, 69.8% (757/1085) completed the test-pathway. This was 74.4% in the most recent year. Younger patients, patients diagnosed in year three or four, patients with high-grade serous/high-grade endometrioid carcinoma, advanced stage disease, middle or high socioeconomic status, and patients who underwent surgery or chemotherapy, were more likely to complete the test-pathway. We report inequalities in genetic testing access in EOC patients, which highlight the need for better guideline adherence, particularly in older patients, those with low socioeconomic status, low-grade histotypes, early-stage disease and those without surgery or chemotherapy. Additionally, timely testing of patients, and testing relatives if patients cannot be tested, are crucial to increase test uptake.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Major membrane protein of Mycobacterium avium subp. paratuberculosis activates immune and autophagic pathways in bovine monocyte-derived macrophages - Jong Hyuk Kim; Donghee Lee; Kevin Hall; Hyunji Jo; John P. Bannantine; William C. Davis; Cleverson de Souza (Veterinary Immunology and Immunopathology, 2025)

Simple GCM Simulations of Rainfall Over Northeast Brazil, Part 2: Model Performance for Historical Seasonal Forecasts - Francisco das Chagas Vasconcelos Junior; Nicholas M. J. Hall; Leticia Cardoso; Aubains Hounsou‐Gbo; Eduardo S. P. R. Martins (International Journal of Climatology, 2025)
A dynamical model is used as a simple GCM to perform historical forecasts for rainfall in northeastern Brazil for the years 1982–2020. The model is forced by empirically derived source terms and includes basic parameterisations to simulate vertical diffusion, convection and condensation. Ensemble forecasts with 38 members are initiated on 1st January using persisted tropical sea surface temperature anomalies (SSTAs). Rainfall forecast performance is evaluated for the February–April (FMA) rainy season. The model reproduces the climatological precipitation in the specified Nordeste region with a mainly dry bias as the model rainfall maximum is displaced in the the northwest. Hindcasts for interannual rainfall anomalies correlate with observed values ( r = 0.46) and model variance is weaker than observed. A further set of forecast experiments with SSTAs restricted to the three major ocean basins reveals that most of the forecast skill can be attributed to the Pacific, despite the model's greater sensitivity to Atlantic SSTAs. The sum of results from the three ocean basins is close to the full hindcast result. Finally, a set of 128 forecast runs with idealised SSTAs placed regularly within the tropics is carried out to calibrate the response of modelled rainfall to remote influences. An influence function is diagnosed in the form of a tropical distribution of northeastern Brazil rainfall in mm/day per unit SSTA. It is strongly concentrated in the tropical Atlantic, with dry/wet conditions resulting from positive SSTAs in the northern/southern tropical Atlantic, in keeping with the observed covariance. The influence function is the used to construct a linear approximation to the forecast performance of the simple GCM. It has similar skill but stronger variance, and the skill is partitioned differently between Atlantic and Pacific influences.

The effect of training paradigm on dogs’ (Canis familiaris) acquisition and generalization of smokeless powders - S.A. Kane; G.N. Cupp; M. Rangel; A. Medrano; J. Davis-Miller; C. Collins-Pisano; B. Rogers; D. Copeland; L. Lazarowski; P. Waggoner; E.O. Aviles-Rosa; P.A. Prada-Tiedemann; et al. (Applied Animal Behaviour Science, 2025)

Consistent Individual Differences and Plasticity in Migration Behaviour of Three North American Ungulates - Michel P. Laforge; Eric Vander Wal; Quinn M. R. Webber; Chris Geremia; Matthew J. Kauffman; Douglas E. McWhirter; Arthur Middleton; Tony W. Mong; Kevin L. Monteith; Anna C. Ortega; Hall Sawyer; Jerod A. Merkle (Ecology Letters, 2025)
Migratory herbivores often time spring migration to coincide with the green‐up of plants. When the timing of green‐up changes across years, herbivores can respond directly and be plastic to changing conditions or populations may adapt via inherent differences among individuals that may allow for an evolutionary response. We quantified plasticity and individual variation in the timing of spring migration and selection for high‐quality forage as a function of the timing of spring green‐up using behavioural reaction norms for three North American ungulate species. The timing of arrival to summer range (but not departure from winter range) was plastic to the timing of green‐up, and both arrival and departure timing were repeatable. Our results suggest that herbivores synchronise migration with the timing of green‐up by adjusting the pace of migration and may be buffered against change via individual differences. Quantifying plasticity and differences in responses represents a crucial step to elucidating the fate of species in a changing world.

Integrated biostratigraphy, chemostratigraphy and geochronology of the lower Cambrian succession in the western Stansbury Basin, South Australia - J. Castle-Jones; M. J. Betts; J. D. Holmes; R. M. Klaebe; P. A. Hall; J. L. Crowley; Z.-L. Zhang; G. A. Brock (Australian Journal of Earth Sciences, 2025)

Differential Attraction of Summer and Winter Morphs of Spotted Wing Drosophila, Drosophila suzukii, to Yeasts - Rory Jones; Matthew R. Goddard; Paul E. Eady; David R. Hall; Daniel P. Bray; Dudley I. Farman; Michelle T. Fountain (Journal of Chemical Ecology, 2025)
Drosophila suzukii is a pest of soft and stone fruits that is attracted to yeast volatile metabolites. Drosophila suzukii has distinct summer and winter morphs which are found in different habitats. Complex communities of yeasts likely differ between habitats and thus we hypothesized morphs differ in their attraction to yeast volatiles from different species and combinations of species. We presented D. suzukii with yeast species in isolation and in combinations, as either post-culture mixes or co-cultured, and measured activity of the flies in laboratory choice tests with a Locomotor Activity Monitor as a proxy for attraction. Candida zemplinina was more attractive to winter than summer morphs when cultured in both sterile strawberry juice (SSJ) and artificial culture media (YPD). No significant correlations were found between principle component scores derived from single yeast volatile profiles and fly activity. There was also differential attraction of morphs to certain yeast mixes, most notably post SSJ culture mixes of Hanseniaspora uvarum and C. zemplinina were consistently more attractive to winter morphs. Mixtures of Metschnikowia pulcherrima + Pichia pijperi + H. uvarum in SSJ and M. pulcherrima + P. pijperi yeasts in YPD were also preferred by winter morphs, whilst summer morphs were attracted to SSJ co-cultures of M. pulcherrima + H. uvarum . However, co-culturing yeasts did not enhance attraction compared to post-culture mixes of constituent yeasts for either morph. Differential attraction of morphs to certain yeasts suggests options for new bait formulations in integrated pest management strategies may be tailored to better target morphs.

Comment on Functional landscape connectivity for a select few: Linkages do not consistently predict wildlife movement or occupancy. Autumn R. Iverson, David Waetjen, Fraser Shilling - A.T.H. Keeley; P. Beier; R.T. Belote; M. Clark; A.P. Clevenger; T.G. Creech; L. Ehlers; J. Faselt; M. Gogol-Prokurat; K.R. Hall; M.A. Hardy; J.A. Hilty; et al. (Landscape and Urban Planning, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Effects of Supranutritional Selenium Supplementation During Different Trimesters of Pregnancy on Humoral Immunity in Beef Cattle at Parturition - Jean A. Hall; Gerd Bobe; William R. Vorachek; Joseph J. Klopfenstein; Ian O. Thompson; Cindy L. Zurita Cruz; Brian P. Dolan; Ling Jin; T. Zane Davis (Biological Trace Element Research, 2024)

Effects of climate change on growth and otolith thermometry of sand whiting (Sillago ciliata) - Melissa Tan; Sebastian Litchfield; Karina C. Hall; Lewis Adler; Brendan P. Kelaher (Geochimica et Cosmochimica Acta, 2024)

Toxicity of rare earth elements (REEs) to marine organisms: Using species sensitivity distributions to establish water quality guidelines for protecting marine life - Scott J. Markich; Jeremy P. Hall; Jude M. Dorsman; Paul L. Brown (Environmental Research, 2024)

Reconciling short- and long-term measurements of coastal cliff erosion rates - Lovleen Acharya-Chowdhury; Mark E. Dickson; Kevin P. Norton; Julie V. Rowland; Brendan Hall; Wayne J. Stephenson (Engineering Geology, 2024)

Activity patterns of Octopus tetricus (Mollusca: Cephalopoda) and their behavioural responses to fisheries trap and bait combinations - Adam A. Vrandich; Brendan P. Kelaher; Karina C. Hall (Marine Biology, 2024)
An understanding of octopus behaviour and their capture by fishing gears is required to inform efficient, sustainable, and ethical octopus fisheries. Here, the behaviour of Octopus tetricus was assessed in response to different bait and trap combinations in an outdoor mesocosm experiment. Eight wild octopuses were collected, maintained in individual tanks with flow-through seawater and aeration, and monitored with a 24-h video surveillance system. Six different traps and four different baits were presented to each octopus in various combinations during four sequential trials. Fine-mesh crab traps were the most successful in capturing octopus, accounting for 23 of the total 30 captures across all trials. Whereas solid trigger traps produced the greatest number of other interactions (e.g., octopus sitting on trap/in the entrance), averaging 43 interactions per trial, but were rarely triggered. Bait type did not influence octopus capture, trap interaction frequency, or octopus activity; however, only artificial bait types were trialled, and fresh natural baits may elicit a stronger response and should be investigated in future research. Generally, octopus were inactive, dedicating only 9.5% of their total time to active behaviours. Octopus activity varied with time of day, with peak activity during morning daylight (0800–1200) and the lowest activity during the dark hours of the very early morning (0000–0400). Additionally, capture numbers, trap interactions, and activity varied among individuals, with bolder personalities in some octopus. This natural variation among individual octopuses may lead to fishery-induced selection associated with the elevated capture frequency of bold or more active individuals.

Water temperature affects somatic growth, body condition and oxygen and carbon otolith isotopes of stout whiting (Sillago robusta) - Melissa Tan; Karina C. Hall; Sebastian Litchfield; Curtis Champion; Matheus Carvalho de Carvalho; Benjamin Mos; Symon Dworjanyn; Brendan P. Kelaher (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Post-release survival of loggerhead sea turtles (Caretta caretta) incidentally hooked in a North Atlantic pelagic longline fishery - Michael C. James; Kelly E. Hall; Emily P. Bond; Scott Sherrill-Mix; Virginie Plot (Frontiers in Marine Science, 2024)
Estimating mortality of sea turtles incidentally captured in fishing gear is essential to understanding fishery impacts on sea turtle populations. Loggerhead turtles ( Caretta caretta ) are a component of bycatch in pelagic longline fisheries, including those operating in Atlantic Canada. In this study, we used pop-up satellite archival tags (PSATs) attached to 62 loggerhead turtles incidentally hooked in Atlantic Canadian shallow-set pelagic longline gear (2012–2018) to estimate associated post-release survival. Consistent with conventional fishing practices, hooks were not removed from turtles prior to release. Analysis of diving behaviour, ocean temperature, and ambient light level was used to assign fates to turtles. Post-release survival was calculated using the Kaplan-Meier estimator with right censoring. Based on this method, the annual survival probability of an individual loggerhead post-release is 0.877 ± SE 0.052. While it is commonly assumed that hook location is an important variable in predicting fates of turtles after release, there was no difference in survival of deep-hooked (swallowed hook) versus shallow-hooked turtles. These results indicate higher survivorship among hooked loggerheads captured in shallow-set pelagic longline gear than prevailing wisdom and suggest that at least some of the population impacts on loggerhead turtles conventionally attributed to pelagic longline interactions may be linked to other threats.

P21-07 The Environmental Health Language Collaborative (EHLC): harmonizing toxicology data use and sharing - M. Shatz; J. Wignall; J. Freed; P. Kaplan; C. Duncan; S. Hall; K. Vinsonhaler; H. Bledsoe; C. Schmitt (Toxicology Letters, 2024)

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Sunflower yield gaps and their causes in Argentina - Ignacio M. Rodriguez; Antonio J. Hall; Juan P. Monzon; Jorge L. Mercau; Sofia Gayo; Monica Lopez Pereira; Anibal Cerrudo; Hernán A. Urcola; Carolina B. Troglia; Sebastián Zuil; María Paolini; Gustavo Martini; et al. (Field Crops Research, 2024)

The planetary protection strategy of Mars Sample Return’s Earth Return Orbiter mission - Giuseppe Cataldo; Lorenz Affentranger; Brian G. Clement; Daniel P. Glavin; David W. Hughes; John Hall; Bruno Sarli; Christine E. Szalai (Journal of Space Safety Engineering, 2024)

The acute effects of cannabis, with and without cannabidiol, on attentional bias to cannabis related cues: a randomised, double-blind, placebo-controlled, cross-over study - Daniel Hall; Will Lawn; Shelan Ofori; Katie Trinci; Anya Borissova; Claire Mokrysz; Kat Petrilli; Michael A. P. Bloomfield; Matthew B. Wall; Tom P. Freeman; H. Valerie Curran (Psychopharmacology, 2024)
Rationale Attentional bias to drug-related stimuli is hypothesised to contribute towards addiction. However, the acute effects of Δ9-tetrahydrocannabinol (THC) on attentional bias to cannabis cues, the differential response in adults and adolescents, and the moderating effect of cannabidiol (CBD) are unknown. Objectives Our study investigated (1) the acute effects of vaporised cannabis on attentional bias to cannabis-related images in adults and adolescents and (2) the moderating influences of age and CBD. Methods We conducted a randomised, double-blind, placebo-controlled, cross-over study where three weight-adjusted vaporised cannabis preparations: ‘THC’ (8 mg THC for a 75-kg person), ‘THC + CBD’ (8 mg THC and 24 mg CBD for a 75-kg person) and PLA (matched placebo). Cannabis was administered on 3 separate days to 48 participants, who used cannabis 0.5–3 days/week: 24 adolescents (12 females, aged 16–17) and 24 adults (12 females, aged 26–29). Participants completed a visual probe task with cannabis cues. Our primary outcome was attentional bias to cannabis stimuli, measured using the differential reaction time to a cannabis vs. neutral probe, on 200-ms trials. Results In contrast to hypotheses, attention was directed away from cannabis cues on placebo, and there was a main effect of the drug ( F (2,92) = 3.865, p = 0.024, η 2 p = 0.077), indicating THC administration eliminated this bias. There was no significant impact of CBD nor an age-by-drug interaction. Conclusions Acute THC intoxication eliminated attentional bias away from cannabis cues. There was no evidence of differential response in adolescents compared to adults and no evidence that a moderate vaporised dose of CBD altered the impact of cannabis on attentional bias. Trial registration This study was listed with the US National Library of Medicine and registered on ClinicalTrials.gov, URL: Do Adolescents and Adults Differ in Their Acute Response to Cannabis?—Full Text View—ClinicalTrials.gov , registration number: NCT04851392.

People behind the “pings”; limiting authorship threatens collaboration in telemetry - L. A. Hawkes; P. Davies; A. E. Hall; T. W. Horton; T. Stamp; M. J. Witt; E. V. Sheehan (Journal of Fish Biology, 2024)

Variations in antimicrobial resistance genes present in the rectal faeces of seals in Scottish and Liverpool Bay coastal waters - Eleanor Watson; Scott Hamilton; Nuno Silva; Simon Moss; Craig Watkins; Johanna Baily; Thorsten Forster; Ailsa J. Hall; Mark P. Dagleish (Environmental Pollution, 2024)

Planetary health issues in the developing world: Dynamics between transportation systems, sustainable economic development, and CO2 emissions - Rudra P. Pradhan; Mahendhiran S. Nair; John H. Hall; Sara E. Bennett (Journal of Cleaner Production, 2024)

Age, origin and tectonic controls on rapid recent exhumation of the Sibela Mountains, Bacan, Indonesia - Juliane Hennig-Breitfeld; Robert Hall; Lloyd T. White; H. Tim Breitfeld; Marnie A. Forster; Richard A. Armstrong; Barry P. Kohn (International Journal of Earth Sciences, 2024)
The Sibela Mountains of the island of Bacan in eastern Indonesia contain one of the Earth’s youngest metamorphic complexes that is now exposed at elevations up to 2000 m. New mica 40 Ar/ 39 Ar and apatite (U–Th–Sm)/He data from metamorphic and igneous rocks indicate that these rocks were rapidly exhumed in the Pleistocene (c. 0.7 Ma). Exhumation of the metamorphosed Permo-Triassic basement (c. 249–257 Ma) was accompanied by metamorphism (recorded by schists) as well as partial melting (recorded by c. 1.4 Ma granitic dykes). These processes must have occurred at extremely high cooling and exhumation rates. The rapid exhumation on land was associated with significant subsidence in adjacent basins offshore that reach depths up to 2.4 km. Neogene metamorphic core complexes and other metamorphic complexes are well-known from eastern Indonesia, but they usually record much higher exhumation rates than those reported from older classic metamorphic core complexes found in other parts of the world and require a different formation mechanism. Unlike classic metamorphic core complexes that are characterized by low-angle detachment faults, the Bacan metamorphic rocks were exhumed on steep bounding normal faults forming a rectilinear block pattern. We suggest such complexes are termed metamorphic block complexes (MBC). The Bacan MBC is exceptionally young and like the other east Indonesian complexes was rapidly exhumed during subduction rollback. A flexure formed during arc-arc collision as the Sangihe forearc loaded the Halmahera forearc which reactivated steeply-dipping faults in a rectilinear chocolate block pattern. Graphical abstract

Differences in neuroinflammation in people who started antiretroviral treatment during primary versus chronic HIV infection: an 18kDa Translocator protein (TSPO) positron emission tomography (PET) study - Jasmini Alagaratnam; John P. Thornhill; Zhen Fan; Jaime H. Vera; Jonathan Underwood; Rebecca Hall; Graham Searle; David Owen; Paul Edison; Sarah Fidler; Alan Winston (Journal of NeuroVirology, 2024)
Persistent inflammation is described in people with HIV (PWH) on antiretroviral treatment (ART). Early ART initiation is associated with reduced inflammation. We aimed to evaluate neuroinflammation, using translocator protein (TSPO) [ 11 C]PBR28 PET neuroimaging in PWH who initiated ART during acute HIV (aPWH) versus chronic HIV infection (cPWH) versus a control population. This was a cross-sectional, observational study. All participants underwent [ 11 C]PBR28 PET-CT neuroimaging. Using a two-tissue compartment model, total volume of distribution (V T ) and distribution volume ratios (DVR) using cortical grey matter as a pseudo-reference region at 20 regions of interest (ROIs) were calculated. Differences in V T and DVR were compared between groups using the Kruskall-Wallis test. Seventeen neuro-asymptomatic male PWH on ART (9 aPWH, 8 cPWH) and 8 male control participants (CPs) were included. Median (interquartile range, IQR) age was 40 (30, 46), 44 (41, 47) and 21 (20, 25) years in aPWH, cPWH and CPs, respectively. Median (IQR) CD4 (cells/µL) and CD4:CD8 were 687 (652, 1014) and 1.37 (1.24, 1.42), and 700 (500, 720) and 0.67 (0.64, 0.82) in aPWH and cPWH, respectively. Overall, no significant difference in V T and DVR were observed between the three groups at any ROIs. cPWH demonstrated a trend towards higher mean V T compared with aPWH and CPs at most ROIs. No significant differences in neuroinflammation, using [ 11 C]PBR28 binding as a proxy, were identified between cPWH, aPWH and CPs. A trend towards lower absolute [ 11 C]PBR28 binding was seen amongst aPWH and CPs, suggesting early ART may mitigate neuroinflammation.

Exposure to Sublethal Concentrations of Lead (Pb) Affects Ecologically Relevant Behaviors in House Sparrows (Passer domesticus) - Joseph F. Di Liberto; Simon C. Griffith; Cara J. Hall; Alexandra S. Mendelsohn; John P. Swaddle (Archives of Environmental Contamination and Toxicology, 2024)
Global contamination of environments with lead (Pb) poses threats to many ecosystems and populations. While exposure to Pb is toxic at high concentrations, recent literature has shown that lower concentrations can also cause sublethal, deleterious effects. However, there remains relatively little causal investigation of how exposure to lower concentrations of environmental Pb affects ecologically important behaviors. Behaviors often represent first-line responses of an organism and its internal physiological, molecular, and genetic responses to a changing environment. Hence, better understanding how behaviors are influenced by pollutants such as Pb generates crucial information on how species are coping with the effects of pollution more broadly. To better understand the effects of sublethal Pb on behavior, we chronically exposed adult wild-caught, captive house sparrows ( Passer domesticus ) to Pb-exposed drinking water and quantified a suite of behavioral outcomes: takeoff flight performance, activity in a novel environment, and in-hand struggling and breathing rate while being handled by an experimenter. Compared to controls (un-exposed drinking water), sparrows exposed to environmentally relevant concentrations of Pb exhibited decreases in takeoff flight performance and reduced movements in a novel environment following 9–10 weeks of exposure. We interpret this suite of results to be consistent with Pb influencing fundamental neuro-muscular abilities, making it more difficult for exposed birds to mount faster movements and activities. It is likely that suppression of takeoff flight and reduced movements would increase the predation risk of similar birds in the wild; hence, we also conclude that the effects we observed could influence fitness outcomes for individuals and populations altering ecological interactions within more naturalistic settings.

Calculating a Land Carbon Accounting Factor in the United States: an Example and Implications - Stephen P Prisley; Edie Sonne Hall (Journal of Forestry, 2024)
Companies that produce and use wood for products and energy find it increasingly important to communicate the carbon balance and potential climate effects of these activities. Computing forest carbon stocks and stock changes, and emissions from operations, are often part of institutional reporting for environmental, social, and governance purposes. This article describes an example methodology to assess forest carbon changes associated with the harvesting of wood products and proposes metrics that could be used to allocate harvesting effects to individual organizations for their reporting purposes. We discuss boundaries (types of forests and carbon pools to include), spatially appropriate evaluations given uncertainty, temporal considerations, risk of reversals, and allocation of net sequestration to products sourced from the region. We also discuss the complex nature of the biogenic carbon cycle and warn about the appropriate interpretation of this methodology.

Holocene climate and catchment change inferred from the geochemistry of Lashmars Lagoon, Kangaroo Island (Karti/Karta), southern Australia - Lucinda Cameron Duxbury; Lluka Yohanni Johns-Mead; Haidee Cadd; Alexander Francke; Stefan C. Löhr; Wallace Boone Law; Linda Armbrecht; Philip Anthony Hall; Atun Zawadzki; Geraldine E. Jacobsen; Patricia S. Gadd; David P. Child; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The first report of Listeria monocytogenes detected in pinnipeds - Johanna L. Baily; Gavin K. Paterson; Geoffrey Foster; Nicholas J. Davison; Lineke Begeman; Ailsa J. Hall; Mark P. Dagleish (Journal of Comparative Pathology, 2024)

Global dominance of lianas over trees is driven by forest disturbance, climate and topography - Alain Senghor K. Ngute; David S. Schoeman; Marion Pfeifer; Geertje M. F. van der Heijden; Oliver L. Phillips; Michiel van Breugel; Mason J. Campbell; Chris J. Chandler; Brian J. Enquist; Rachael V. Gallagher; Christoph Gehring; Jefferson S. Hall; et al. (Global Change Biology, 2024)
Growing evidence suggests that liana competition with trees is threatening the global carbon sink by slowing the recovery of forests following disturbance. A recent theory based on local and regional evidence further proposes that the competitive success of lianas over trees is driven by interactions between forest disturbance and climate. We present the first global assessment of liana–tree relative performance in response to forest disturbance and climate drivers. Using an unprecedented dataset, we analysed 651 vegetation samples representing 26,538 lianas and 82,802 trees from 556 unique locations worldwide, derived from 83 publications. Results show that lianas perform better relative to trees (increasing liana‐to‐tree ratio) when forests are disturbed, under warmer temperatures and lower precipitation and towards the tropical lowlands. We also found that lianas can be a critical factor hindering forest recovery in disturbed forests experiencing liana‐favourable climates, as chronosequence data show that high competitive success of lianas over trees can persist for decades following disturbances, especially when the annual mean temperature exceeds 27.8°C, precipitation is less than 1614 mm and climatic water deficit is more than 829 mm. These findings reveal that degraded tropical forests with environmental conditions favouring lianas are disproportionately more vulnerable to liana dominance and thus can potentially stall succession, with important implications for the global carbon sink, and hence should be the highest priority to consider for restoration management.

Experiences of and support for black women in ecology, evolution, and marine science - Nikki Traylor-Knowles; Anamica Bedi de Silva; Anjali D. Boyd; Karlisa A. Callwood; Alexandra C. D. Davis; Giselle Hall; Victoria Moreno; Cinda P. Scott (Frontiers in Marine Science, 2023)
Systemic racism and sexism are well documented in ecology, evolution, and marine science. To combat this, institutions are making concerted efforts to recruit more diverse people by focusing on the recruitment of Black people. However, despite these initiatives, white supremacy culture still prevails. The retention of Black people in ecology, evolution, and marine science has not increased in the ways that were hoped for. This is particularly true for Black women, who struggle to find a safe working environment that values their contributions and allows them to openly celebrate their own culture and identity. In this perspective article, we discuss the challenges that Black women face every day, and the needs of Black women to thrive in ecology, evolution, and marine science. We have written this directly to Black women and provide information on not only our challenges, but our stories. However, readers of all identities are welcome to listen and examine their role in perpetuating systemic racism and sexism. Lastly, we discuss support mechanisms for navigating ecology, evolution, and marine science spaces so that Black women can thrive.

Improving the performance of post-consumer resin feedstocks for rigid packaging applications: A pilot-scale assessment - A.R. McLauchlin; D Hall; D Feldman; P Anderson; M Newman; T Hasell; T.O. McDonald (Resources, Conservation and Recycling, 2023)

Nature-based solutions for leveed river corridors - Matthew L. Chambers; Charles B. van Rees; Brian P. Bledsoe; David Crane; Susana Ferreira; Damon M. Hall; Rod W. Lammers; Craig E. Landry; Donald R. Nelson; Matt Shudtz; Burton C. Suedel (Anthropocene, 2023)

Antioxidants green tea extract and nordihydroguaiaretic acid confer species and strain-specific lifespan and health effects in Caenorhabditis nematodes - Stephen A. Banse; Christine A. Sedore; Erik Johnson; Anna L. Coleman-Hulbert; Brian Onken; David Hall; E. Grace Jackson; Phu Huynh; Anna C. Foulger; Suzhen Guo; Theo Garrett; Jian Xue; et al. (GeroScience, 2023)
The Caenorhabditis Intervention Testing Program (CITP) is an NIH-funded research consortium of investigators who conduct analyses at three independent sites to identify chemical interventions that reproducibly promote health and lifespan in a robust manner. The founding principle of the CITP is that compounds with positive effects across a genetically diverse panel of Caenorhabditis species and strains are likely engaging conserved biochemical pathways to exert their effects. As such, interventions that are broadly efficacious might be considered prominent compounds for translation for pre-clinical research and human clinical applications. Here, we report results generated using a recently streamlined pipeline approach for the evaluation of the effects of chemical compounds on lifespan and health. We studied five compounds previously shown to extend C. elegans lifespan or thought to promote mammalian health: 17α-estradiol, acarbose, green tea extract, nordihydroguaiaretic acid, and rapamycin. We found that green tea extract and nordihydroguaiaretic acid extend Caenorhabditis lifespan in a species-specific manner. Additionally, these two antioxidants conferred assay-specific effects in some studies—for example, decreasing survival for certain genetic backgrounds in manual survival assays in contrast with extended lifespan as assayed using automated C. elegans Lifespan Machines. We also observed that GTE and NDGA impact on older adult mobility capacity is dependent on genetic background, and that GTE reduces oxidative stress resistance in some Caenorhabditis strains. Overall, our analysis of the five compounds supports the general idea that genetic background and assay type can influence lifespan and health effects of compounds, and underscores that lifespan and health can be uncoupled by chemical interventions.

Nepalese indoor cookstove smoke extracts alter human airway epithelial gene expression, DNA methylation and hydroxymethylation - Poojitha Rajasekar; Robert J. Hall; K.C. Binaya; Parth S. Mahapatra; Siva P. Puppala; Dhruma Thakker; Julia L. MacIsaac; David Lin; Michael Kobor; Charlotte E. Bolton; Ian Sayers; Ian P. Hall; et al. (Environmental Pollution, 2023)

The influence of biochar position in a leach bed system anaerobically digesting chicken litter - Ben A. Collins; Cristian H. Birzer; Stephen P. Kidd; Tony Hall; Paul R. Medwell (Journal of Environmental Management, 2023)

A novel co-culture model of human prostate epithelial and stromal cells for androgenic and antiandrogenic screening - Hui Li; Samantha Madnick; He Zhao; Susan Hall; Ali Amin; Matthew P. Dent; Kim Boekelheide (Toxicology in Vitro, 2023)

Fine-tuning the CROPGRO-Sunflower model and its application to the quantification of crop responses to environmental and management variables - Ignacio M. Rodriguez; Jorge L. Mercau; Pablo A. Cipriotti; Antonio J. Hall; Juan P. Monzon (Field Crops Research, 2023)

Effects of crustal assimilation on 238U-230Th disequilibria in continental arc settings - L.B. Kant; K.W.W. Sims; G.M. Yogodzinski; J.M. Garrison; J. Blichert-Toft; M. Reagan; C.L. Waters; T.P. Mathews; S.R. Scott; P.A. Mothes; M.L. Hall; P. Ramón; et al. (Geochimica et Cosmochimica Acta, 2023)

Environmental optima for common diatoms from Ontario lakes along gradients of lakewater pH, total phosphorus concentration, and depth - Matthew P. Duda; Branaavan Sivarajah; Kathleen M. Rühland; Andrew M. Paterson; Jennifer L. Barrow; Yuanyu Cheng; Elizabeth J. Favot; Kristopher R. Hadley; Roland I. Hall; Kathryn E. Hargan; Clare Nelligan; Euan D. Reavie; et al. (Journal of Paleolimnology, 2023)

Thallium toxicity to temperate and tropical marine organisms: Derivation of water quality guidelines to protect marine life - Scott J. Markich; Jeremy P. Hall; Jude M. Dorsman; Paul L. Brown (Marine Pollution Bulletin, 2023)

Poriferans rift apart: molecular demosponge biodiversity in Central and French Polynesia and comparison with adjacent marine provinces of the Central Indo-Pacific - Adrian Galitz; Merrick Ekins; Eric Folcher; Gabriele Büttner; Kathryn Hall; John N. A. Hooper; Maggie M. Reddy; Simone Schätzle; Olivier P. Thomas; Gert Wörheide; Sylvain Petek; Cécile Debitus; et al. (Biodiversity and Conservation, 2023)
The distribution of marine sponges in the tropical Southwest Pacific Ocean is largely unexplored despite the vital ecological role of sponges in coral reefs and their value as sources of metabolites for drug design. Several collection campaigns to the French Polynesian archipelagos (Society, Marquesas, Tuamotu, Gambier, and Austral) were conducted to assess the bio- and chemodiversity of the island groups. In the course of these scientific expeditions, more than 200 identified sponge specimens were acquired, for which we were able to assign 102 Molecular Operational Taxonomic Units (MOTUs). Based on these MOTUs, we assessed, in the largest analysis of its kind for this area to date, the sponge composition and faunistic overlaps of the marine province Southeast Polynesia with Marquesas and Central Polynesia. We also compared the sponge fauna of these Eastern Indo-Pacific provinces with marine provinces of the adjacent Central Indo-Pacific realm. Our findings corroborate that sponge faunal similarity within marine realms is higher than among realms, and follows the marine barriers to gene flow observed for other taxa. We detected high levels of provincial endemism for marine sponges, consistent with findings from other Indo-Pacific regions. At the level of province, geographical distance and ocean surface currents influence faunal similarity, and constitute the primary factors for the connectivity of sponge faunas between the disjunct and remote island groups in the tropical Southwest Pacific Ocean.

Ocean acidification stunts molluscan growth at CO2 seeps - Liqiang Zhao; Ben P. Harvey; Tomihiko Higuchi; Sylvain Agostini; Kentaro Tanaka; Naoko Murakami-Sugihara; Holly Morgan; Phoebe Baker; Jason M. Hall-Spencer; Kotaro Shirai (Science of The Total Environment, 2023)

Inferred vehicular emissions at a near-road site: Impacts of COVID-19 restrictions, traffic patterns, and ambient air temperature - Dolly L. Hall-Quinlan; Hao He; Xinrong Ren; Timothy P. Canty; Ross J. Salawitch; Phillip Stratton; Russell R. Dickerson (Atmospheric Environment, 2023)

Ocean acidification increases the impact of typhoons on algal communities - Callum J. Hudson; Sylvain Agostini; Shigeki Wada; Jason M. Hall-Spencer; Sean D. Connell; Ben P. Harvey (Science of The Total Environment, 2023)

Gestational organophosphate ester exposure and preschool attention-deficit/hyperactivity disorder in the Norwegian Mother, Father, and Child cohort study - Amber M. Hall; Amanda M. Ramos; Samantha SM. Drover; Giehae Choi; Alexander P. Keil; David B. Richardson; Chantel L. Martin; Andrew F. Olshan; Gro D. Villanger; Ted Reichborn-Kjennerud; Pål Zeiner; Kristin R. Øvergaard; et al. (International Journal of Hygiene and Environmental Health, 2023)

Aluminium-normalised trace-element paleoredox proxies and their application to the study of the conditions of Burgess Shale-type preservation - K. C. Meehan; W. G. Powell; D. M. McKirdy; P. A. Hall; C. Nedin; P. A. Johnston; C. J. Collom (Australian Journal of Earth Sciences, 2023)

Coupling a biochar filter to a leach bed reactor for anaerobic digestion of chicken litter - Ben A. Collins; Cristian H. Birzer; Stephen P. Kidd; Tony Hall; Paul R. Medwell (Bioresource Technology Reports, 2023)

Neuroimaging and immunological features of neurocognitive function related to substance use in people with HIV - David M. Murdoch; Richard Barfield; Cliburn Chan; Sheri L. Towe; Ryan P. Bell; Alicia Volkheimer; Joyce Choe; Shana A. Hall; Miles Berger; Jichun Xie; Christina S. Meade (Journal of NeuroVirology, 2023)

Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region - Benjamin S. Jordan; Jason D. Readle; Jeffrey R. Cooper; Matthew Cook; Jason P. Hayward; J. Daniel Hartman; Dean Forrest; Howard L. Hall (Annals of Nuclear Energy, 2023)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Components of the Female Sex Pheromone of the Newly-Described Canola Flower Midge, Contarinia brassicola - Daniel P. Bray; David R. Hall; Steven J. Harte; Dudley I. Farman; Meghan A. Vankosky; Boyd A. Mori (Journal of Chemical Ecology, 2022)
The canola flower midge, Contarinia brassicola Sinclair (Diptera: Cecidomyiidae), is a newly-described species that induces galls on canola, Brassica napus Linnaeus and Brassica rapa Linnaeus (Brassicaceae). Identification of the sex pheromone of C. brassicola is essential to developing monitoring tools to elucidate the geographic range and hosts of this new pest, and the extent to which it threatens the $30 billion Canadian canola industry. The aim of this study was to identify and synthesize the female-produced sex pheromone of C. brassicola and demonstrate its effectiveness in attracting males to traps in the field. Two peaks were identified through GC-EAG analysis of female-produced volatiles which elicited electrophysiological responses in male antennae. These peaks were initially characterized through GC–MS and synthesis as 2,7-diacetoxynonane (major component) and 2-acetoxynonane (minor component), and the racemic compounds elicited EAG responses in male antennae. All four stereoisomers of 2,7-diacetoxynonane were synthesized and the naturally-produced compound was shown to be primarily the (2 R, 7 S )-isomer by analysis on an enantioselective GC column, with a small amount of (2 R, 7 R )-2,7-diacetoxynonane also present. The configuration of the minor component could not be determined because of the small amount present, but this was assumed to be (2 R )-2-acetoxynonane by comparison with the configuration of the other two components. In field trials, none of the four stereoisomers of 2,7-diacetoxynonane, presented individually or as a racemic mixture, was attractive to male C. brassicola . However, dispensers loaded with a 10 µg:1 µg blend of (2 R, 7 S )- and (2 R, 7 R )-2,7-diacetoxynonane caught large numbers of male C. brassicola and significantly more than other blends tested. The addition of 0.5 µg of (2 R )-2-acetoxynonane to this blend further increased the number of males caught. In future work, we will seek to identify the optimum trapping protocol for the application of the pheromone in monitoring and surveillance.

Anthropogenic Mixing in Seasonally Stratified Shelf Seas by Offshore Wind Farm Infrastructure - Robert M. Dorrell; Charlie J. Lloyd; Ben J. Lincoln; Tom P. Rippeth; John R. Taylor; Colm-cille P. Caulfield; Jonathan Sharples; Jeff A. Polton; Brian D. Scannell; Deborah M. Greaves; Rob A. Hall; John H. Simpson (Frontiers in Marine Science, 2022)
The offshore wind energy sector has rapidly expanded over the past two decades, providing a renewable energy solution for coastal nations. Sector development has been led in Europe, but is growing globally. Most developments to date have been in well-mixed, i.e., unstratified, shallow-waters near to shore. Sector growth is, for the first time, pushing developments to deep water, into a brand new environment: seasonally stratified shelf seas. Seasonally stratified shelf seas, where water density varies with depth, have a disproportionately key role in primary production, marine ecosystem and biogeochemical cycling. Infrastructure will directly mix stratified shelf seas. The magnitude of this mixing, additional to natural background processes, has yet to be fully quantified. If large enough it may erode shelf sea stratification. Therefore, offshore wind growth may destabilize and fundamentally change shelf sea systems. However, enhanced mixing may also positively impact some marine ecosystems. This paper sets the scene for sector development into this new environment, reviews the potential physical and environmental benefits and impacts of large scale industrialization of seasonally stratified shelf seas and identifies areas where research is required to best utilize, manage, and mitigate environmental change.

Protective role of lactic acid bacteria and yeasts as dietary carcinogen-binding agents – a review - P. F. Cuevas-González; A. F. González-Córdova; B. Vallejo-Cordoba; J. E. Aguilar-Toalá; F. G. Hall; U. C. Urbizo-Reyes; A. M. Liceaga; A. Hernandez-Mendoza; H. S. García (Critical Reviews in Food Science and Nutrition, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Understanding coralline algal responses to ocean acidification: Meta‐analysis and synthesis - Christopher E. Cornwall; Ben P. Harvey; Steeve Comeau; Daniel L. Cornwall; Jason M. Hall‐Spencer; Viviana Peña; Shigeki Wada; Lucia Porzio (Global Change Biology, 2022)
Ocean acidification (OA) is a major threat to the persistence of biogenic reefs throughout the world's ocean. Coralline algae are comprised of high magnesium calcite and have long been considered one of the most susceptible taxa to the negative impacts of OA. We summarize these impacts and explore the causes of variability in coralline algal responses using a review/qualitative assessment of all relevant literature, meta‐analysis, quantitative assessment of critical responses, and a discussion of physiological mechanisms and directions for future research. We find that most coralline algae experienced reduced abundance, calcification rates, recruitment rates, and declines in pH within the site of calcification in laboratory experiments simulating OA or at naturally elevated CO 2 sites. There were no other consistent physiological responses of coralline algae to simulated OA (e.g., photo‐physiology, mineralogy, and survival). Calcification/growth was the most frequently measured parameters in coralline algal OA research, and our meta‐analyses revealed greater declines in seawater pH were associated with significant decreases in calcification in adults and similar but nonsignificant trends for juveniles. Adults from the family Mesophyllumaceae also tended to be more robust to OA, though there was insufficient data to test similar trends for juveniles. OA was the dominant driver in the majority of laboratory experiments where other local or global drivers were assessed. The interaction between OA and any other single driver was often additive, though factors that changed pH at the surface of coralline algae (light, water motion, epiphytes) acted antagonistically or synergistically with OA more than any other drivers. With advances in experimental design and methodological techniques, we now understand that the physiology of coralline algal calcification largely dictates their responses to OA. However, significant challenges still remain, including improving the geographic and life‐history spread of research effort and a need for holistic assessments of physiology.

A systematic review of in vitro studies evaluating the inhibitory effects of polyphenol-rich fruit extracts on carbohydrate digestive enzymes activity: a focus on culinary fruits consumed in Europe - E. J. Prpa; B. H. Bajka; P. R. Ellis; P. J. Butterworth; C. P. Corpe; W. L. Hall (Critical Reviews in Food Science and Nutrition, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Ancient horse genomes reveal the timing and extent of dispersals across the Bering Land Bridge - Alisa O. Vershinina; Peter D. Heintzman; Duane G. Froese; Grant Zazula; Molly Cassatt‐Johnstone; Love Dalén; Clio Der Sarkissian; Shelby G. Dunn; Luca Ermini; Cristina Gamba; Pamela Groves; Joshua D. Kapp; et al. (Molecular Ecology, 2021)
The Bering Land Bridge (BLB) last connected Eurasia and North America during the Late Pleistocene. Although the BLB would have enabled transfers of terrestrial biota in both directions, it also acted as an ecological filter whose permeability varied considerably over time. Here we explore the possible impacts of this ecological corridor on genetic diversity within, and connectivity among, populations of a once wide‐ranging group, the caballine horses ( Equus spp.). Using a panel of 187 mitochondrial and eight nuclear genomes recovered from present‐day and extinct caballine horses sampled across the Holarctic, we found that Eurasian horse populations initially diverged from those in North America, their ancestral continent, around 1.0–0.8 million years ago. Subsequent to this split our mitochondrial DNA analysis identified two bidirectional long‐range dispersals across the BLB ~875–625 and ~200–50 thousand years ago, during the Middle and Late Pleistocene. Whole genome analysis indicated low levels of gene flow between North American and Eurasian horse populations, which probably occurred as a result of these inferred dispersals. Nonetheless, mitochondrial and nuclear diversity of caballine horse populations retained strong phylogeographical structuring. Our results suggest that barriers to gene flow, currently unidentified but possibly related to habitat distribution across Beringia or ongoing evolutionary divergence, played an important role in shaping the early genetic history of caballine horses, including the ancestors of living horses within Equus ferus .

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Biogeochemical status of the Paleo-Pacific Ocean: clues from the early Cambrian of South Australia - P. A. Hall; D. M. McKirdy; G. P. Halverson; J. B. Jago; A. S. Collins (Australian Journal of Earth Sciences, 2021)

Major loss of coralline algal diversity in response to ocean acidification - Viviana Peña; Ben P. Harvey; Sylvain Agostini; Lucia Porzio; Marco Milazzo; Paulo Horta; Line Le Gall; Jason M. Hall‐Spencer (Global Change Biology, 2021)
Calcified coralline algae are ecologically important in rocky habitats in the marine photic zone worldwide and there is growing concern that ocean acidification will severely impact them. Laboratory studies of these algae in simulated ocean acidification conditions have revealed wide variability in growth, photosynthesis and calcification responses, making it difficult to assess their future biodiversity, abundance and contribution to ecosystem function. Here, we apply molecular systematic tools to assess the impact of natural gradients in seawater carbonate chemistry on the biodiversity of coralline algae in the Mediterranean and the NW Pacific, link this to their evolutionary history and evaluate their potential future biodiversity and abundance. We found a decrease in the taxonomic diversity of coralline algae with increasing acidification with more than half of the species lost in high p CO 2 conditions. Sporolithales is the oldest order (Lower Cretaceous) and diversified when ocean chemistry favoured low Mg calcite deposition; it is less diverse today and was the most sensitive to ocean acidification. Corallinales were also reduced in cover and diversity but several species survived at high p CO 2 ; it is the most recent order of coralline algae and originated when ocean chemistry favoured aragonite and high Mg calcite deposition. The sharp decline in cover and thickness of coralline algal carbonate deposits at high p CO 2 highlighted their lower fitness in response to ocean acidification. Reductions in CO 2 emissions are needed to limit the risk of losing coralline algal diversity.

Simplification, not “tropicalization”, of temperate marine ecosystems under ocean warming and acidification - Sylvain Agostini; Ben P. Harvey; Marco Milazzo; Shigeki Wada; Koetsu Kon; Nicolas Floc’h; Kosei Komatsu; Mayumi Kuroyama; Jason M. Hall‐Spencer (Global Change Biology, 2021)
Ocean warming is altering the biogeographical distribution of marine organisms. In the tropics, rising sea surface temperatures are restructuring coral reef communities with sensitive species being lost. At the biogeographical divide between temperate and tropical communities, warming is causing macroalgal forest loss and the spread of tropical corals, fishes and other species, termed “tropicalization”. A lack of field research into the combined effects of warming and ocean acidification means there is a gap in our ability to understand and plan for changes in coastal ecosystems. Here, we focus on the tropicalization trajectory of temperate marine ecosystems becoming coral‐dominated systems. We conducted field surveys and in situ transplants at natural analogues for present and future conditions under (i) ocean warming and (ii) both ocean warming and acidification at a transition zone between kelp and coral‐dominated ecosystems. We show that increased herbivory by warm‐water fishes exacerbates kelp forest loss and that ocean acidification negates any benefits of warming for range extending tropical corals growth and physiology at temperate latitudes. Our data show that, as the combined effects of ocean acidification and warming ratchet up, marine coastal ecosystems lose kelp forests but do not gain scleractinian corals. Ocean acidification plus warming leads to overall habitat loss and a shift to simple turf‐dominated ecosystems, rather than the complex coral‐dominated tropicalized systems often seen with warming alone. Simplification of marine habitats by increased CO 2 levels cascades through the ecosystem and could have severe consequences for the provision of goods and services.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Understory physical structures reduce browsing damage to palatable shrubs in a dry conifer forest, western North America - Dallas Hall Defrees; Joshua P. Averett; Bryan A. Endress (Plant Ecology, 2021)

Neuropsychological Assessment and Screening in Heart Failure: a Meta-Analysis and Systematic Review - Eric J. Connors; Alexander O. Hauson; Brianna D. Barlet; Sharis Sarkissians; Nicholas P. Stelmach; Alyssa D. Walker; Natasha M. Nemanim; Kristina L. Greenwood; Nicholas J. Chesher; Scott C. Wollman; Kenneth E. Allen; Matthew G. Hall; et al. (Neuropsychology Review, 2021)

Development and Interrogation of a Transcriptomic Resource for the Giant Triton Snail (Charonia tritonis) - AH Klein; CA Motti; AK Hillberg; T Ventura; P Thomas-Hall; T Armstrong; T Barker; P Whatmore; SF Cummins (Marine Biotechnology, 2021)
Gastropod molluscs are among the most abundant species that inhabit coral reef ecosystems. Many are specialist predators, along with the giant triton snail Charonia tritonis (Linnaeus, 1758) whose diet consists of Acanthaster planci (crown-of-thorns starfish), a corallivore known to consume enormous quantities of reef-building coral. C. tritonis are considered vulnerable due to overexploitation, and a decline in their populations is believed to have contributed to recurring A. planci population outbreaks. Aquaculture is considered one approach that could help restore natural populations of C. tritonis and mitigate coral loss; however, numerous questions remain unanswered regarding their life cycle, including the molecular factors that regulate their reproduction and development. In this study, we have established a reference C. tritonis transcriptome derived from developmental stages (embryo and veliger) and adult tissues. This was used to identify genes associated with cell signalling, such as neuropeptides and G protein-coupled receptors (GPCRs), involved in endocrine and olfactory signalling. A comparison of developmental stages showed that several neuropeptide precursors are exclusively expressed in post-hatch veligers and functional analysis found that FFamide stimulated a significant (20.3%) increase in larval heart rate. GPCRs unique to veligers, and a diversity of rhodopsin-like GPCRs located within adult cephalic tentacles, all represent candidate olfactory receptors. In addition, the cytochrome P450 superfamily, which participates in the biosynthesis and degradation of steroid hormones and lipids, was also found to be expanded with at least 91 genes annotated, mostly in gill tissue. These findings further progress our understanding of C. tritonis with possible application in developing aquaculture methods.

Institutional Review Board Preparedness for Disaster Research: a Practical Approach - Joan P. Packenham; Richard Rosselli; Alice Fothergill; Julia Slutsman; Steve Ramsey; Janet E. Hall; Aubrey Miller (Current Environmental Health Reports, 2021)
Purpose of Review Disasters are becoming more common and challenge national and global resiliency and response efforts. As a result, government agencies have increased interest in disaster research to understand their environmental impact and health-related consequences. With the research field greatly expanding, Institutional Review Boards (IRBs) are being asked to review research protocols aimed at assessing health risks, exposures, and outcomes from disaster survivors. Few IRBs have experience reviewing disaster research protocols. This article describes approaches for IRB preparedness in reviewing disaster research. Recent Findings From a human research protections perspective, primary attention has focused on vulnerability of individuals and/or populations affected by a disaster who may serve as research participants [3, 4]. From our review of the current literature, there is a lack of best practices and/or guidance for IRBs in the review of disaster research protocols. Summary The growth of the disaster research field has brought more attention to potential ethical concerns of disaster research studies. Disaster survivors, responders, and those that assist in cleanup and remedial efforts may be left with significant unmet needs and long-term physical and emotional challenges as a result of their experiences. It is important for IRBs and investigators to collaboratively address how best to protect the welfare of individuals and communities affected by a disaster. A new approach is needed to systematically consider the various factors relevant to an assessment of human research protection issues following disasters.

Early indications of success rehabilitating an underperforming teak (Tectona grandis) plantation in Panama through enrichment planting - Abigail Marshall; Bailey P. McLaughlin; Camilla Zerr; Estrella Yanguas-Fernández; Jefferson S. Hall (New Forests, 2021)
Enrichment planting can be an effective strategy for increasing the ecological and economic value of timber plantations, but success depends on appropriate matching of under- and overstory species and site conditions. This case study in the Panama Canal Watershed explores the viability of enrichment planting for rehabilitating underperforming teak ( Tectonia grandis) plantations, which are common in the area. Two high-value timber species native to the neotropics, Dalbergia retusa and Terminalia amazonia, were underplanted in an established teak plantation at the Agua Salud research site in the province of Colon, Panama. Seedling survival, basal diameter, height, total biomass and relative growth rate were assessed for the two years following planting. In contrast with the widespread belief that teak is a poor nurse tree, both species achieved promising early growth with low mortality in plantation understory conditions. Neither understory light availability nor combined above- and below-ground effects of crowding pressure from teak strongly predicted growth of either species. D. retusa, thought to be more shade-tolerant, performed equally across a range of intermediate light levels whereas T. amazonia, thought to be more heliotropic, performed best at the highest light levels, though light relationships explained little variation in seedling growth. These early findings support the suitability of either species for use in enrichment plantings in established, underperforming teak plantations in the Panama Canal Watershed. Longer-term research is needed to evaluate the potential of enrichment planting to increase profitability and ecosystem services such as carbon sequestration and water resource management in these plantations.

In vivo Validation of Bimolecular Fluorescence Complementation (BiFC) to Investigate Aggregate Formation in Amyotrophic Lateral Sclerosis (ALS) - Emily K. Don; Alina Maschirow; Rowan A. W. Radford; Natalie M. Scherer; Andrés Vidal-Itriago; Alison Hogan; Cindy Maurel; Isabel Formella; Jack J. Stoddart; Thomas E. Hall; Albert Lee; Bingyang Shi; et al. (Molecular Neurobiology, 2021)
Amyotrophic lateral sclerosis (ALS) is a form of motor neuron disease (MND) that is characterized by the progressive loss of motor neurons within the spinal cord, brainstem, and motor cortex. Although ALS clinically manifests as a heterogeneous disease, with varying disease onset and survival, a unifying feature is the presence of ubiquitinated cytoplasmic protein inclusion aggregates containing TDP-43. However, the precise mechanisms linking protein inclusions and aggregation to neuronal loss are currently poorly understood. Bimolecular fluorescence complementation (BiFC) takes advantage of the association of fluorophore fragments (non-fluorescent on their own) that are attached to an aggregation-prone protein of interest. Interaction of the proteins of interest allows for the fluorescent reporter protein to fold into its native state and emit a fluorescent signal. Here, we combined the power of BiFC with the advantages of the zebrafish system to validate, optimize, and visualize the formation of ALS-linked aggregates in real time in a vertebrate model. We further provide in vivo validation of the selectivity of this technique and demonstrate reduced spontaneous self-assembly of the non-fluorescent fragments in vivo by introducing a fluorophore mutation. Additionally, we report preliminary findings on the dynamic aggregation of the ALS-linked hallmark proteins Fus and TDP-43 in their corresponding nuclear and cytoplasmic compartments using BiFC. Overall, our data demonstrates the suitability of this BiFC approach to study and characterize ALS-linked aggregate formation in vivo. Importantly, the same principle can be applied in the context of other neurodegenerative diseases and has therefore critical implications to advance our understanding of pathologies that underlie aberrant protein aggregation.

Hero Turned Villain: Identification of Components of the Sex Pheromone of the Tomato Bug, Nesidiocoris tenuis - David R. Hall; Steven J. Harte; Daniel P. Bray; Dudley I. Farman; Rob James; Celine X. Silva; Michelle T. Fountain (Journal of Chemical Ecology, 2021)
Nesidiocoris tenuis (Reuter) (Heteroptera: Miridae) is a tropical mirid bug used as a biocontrol agent in protected crops, including tomatoes. Although N. tenuis predates important insect pests, especially whitefly, it also causes damage by feeding on tomato plants when prey populations decline, resulting in significant economic losses for growers. The pest is now established in some all-year-round tomato crops in Europe and control measures involve the application of pesticides which are incompatible with current IPM programs. As part of future IPM strategies, the pheromone of N. tenuis was investigated. Volatile collections were made from groups and individuals of mated and unmated, females and males. In analyses of these collections by gas chromatography coupled with electroantennographic (EAG) recording from antennae of male bugs, two EAG-active components were detected and identified as 1-octanol and octyl hexanoate. Unlike other mirids, both male and female N. tenuis produced the two compounds, before and after mating, and both sexes gave EAG responses to both compounds. Furthermore, only octyl hexanoate was detected in whole body solvent washes from both sexes. These compounds are not related to the derivatives of 3-hydroxybutyrate esters found as pheromone components in other members of the Bryocrinae sub-family, and the latter could not be detected in volatiles from N. tenuis and did not elicit EAG responses. Nevertheless, experiments carried out in commercial glasshouses showed that traps baited with a blend of the synthetic pheromone components caught essentially only male N. tenuis , and significantly more than traps baited with octyl hexanoate alone. The latter caught significantly more N. tenuis than unbaited traps which generally caught very few bugs. Traps at plant height caught more N. tenuis males than traps 1 m above or at the base of the plants. The trap catches provided an indication of population levels of N. tenuis and were greatly reduced following an application of insecticide.

Ocean acidification locks algal communities in a species‐poor early successional stage - Ben P. Harvey; Koetsu Kon; Sylvain Agostini; Shigeki Wada; Jason M. Hall‐Spencer (Global Change Biology, 2021)
Long‐term exposure to CO 2 ‐enriched waters can considerably alter marine biological community development, often resulting in simplified systems dominated by turf algae that possess reduced biodiversity and low ecological complexity. Current understanding of the underlying processes by which ocean acidification alters biological community development and stability remains limited, making the management of such shifts problematic. Here, we deployed recruitment tiles in reference (pH T 8.137 ± 0.056 SD) and CO 2 ‐enriched conditions (pH T 7.788 ± 0.105 SD) at a volcanic CO 2 seep in Japan to assess the underlying processes and patterns of algal community development. We assessed (i) algal community succession in two different seasons (Cooler months: January–July, and warmer months: July–January), (ii) the effects of initial community composition on subsequent community succession (by reciprocally transplanting preestablished communities for a further 6 months), and (iii) the community production of resulting communities, to assess how their functioning was altered (following 12 months recruitment). Settlement tiles became dominated by turf algae under CO 2 ‐enrichment and had lower biomass, diversity and complexity, a pattern consistent across seasons. This locked the community in a species‐poor early successional stage. In terms of community functioning, the elevated p CO 2 community had greater net community production, but this did not result in increased algal community cover, biomass, biodiversity or structural complexity. Taken together, this shows that both new and established communities become simplified by rising CO 2 levels. Our transplant of preestablished communities from enriched CO 2 to reference conditions demonstrated their high resilience, since they became indistinguishable from communities maintained entirely in reference conditions. This shows that meaningful reductions in p CO 2 can enable the recovery of algal communities. By understanding the ecological processes responsible for driving shifts in community composition, we can better assess how communities are likely to be altered by ocean acidification.

Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study - Kalina M. Brauko; Alex Cabral; Natasha V. Costa; Juliana Hayden; Carlos E. P. Dias; Edilene S. Leite; Renan D. Westphal; Carolina M. Mueller; Jason M. Hall-Spencer; Regina R. Rodrigues; Leonardo R. Rörig; Paulo R. Pagliosa; et al. (Frontiers in Marine Science, 2020)
Marine heatwaves (MHWs) are a major concern worldwide due to their increasing impacts in recent years, and these extreme events may trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of MHWs and nutrient enrichment on the water quality and biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994–2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to assess temporal trends. Oxygen levels have been decreasing whilst phosphorus levels have been increasing in the bay. During the austral summer of 2020 a regional sea surface heatwave was detected by satellite, lasting for 9 days and coinciding with our research cruise. During this period, seawater temperatures reached 29.8°C and anoxia was detected for the first time in the bay. A decrease in macrobenthic and phytoplankton community richness correlated with decreases in oxygen both through time and towards more urbanized areas. Overall, poor wastewater treatment is a key stressor that combined with MHWs to degrade coastal waters. Mitigation strategies are needed to minimize the impact of MHWs, including improved sewage treatment, restoration and conservation of wetlands and the use of nature-based technologies to promote coastal ecosystem recovery.

Responses of Intertidal Bacterial Biofilm Communities to Increasing pCO2 - Dorsaf Kerfahi; Ben P. Harvey; Sylvain Agostini; Koetsu Kon; Ruiping Huang; Jonathan M. Adams; Jason M. Hall-Spencer (Marine Biotechnology, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Shedding light on environmentally transmitted parasites: lighter conditions within lakes restrict epidemic size - Clara L. Shaw; Spencer R. Hall; Erin P. Overholt; Carla E. Cáceres; Craig E. Williamson; Meghan A. Duffy (Ecology, 2020)
Parasite fitness depends on a successful journey from one host to another. For parasites that are transmitted environmentally, abiotic conditions might modulate the success of this journey. Here we evaluate how light, a key abiotic factor, influences spatiotemporal patterns of zooplankton disease where light varies seasonally, across lakes, and with depth in a lake. In an in situ experiment using those three sources of variation, we tested sensitivity of spores of two parasites to ambient light. Infectivity of both parasites was lower when exposed to ambient light in comparison to parasites exposed to otherwise similar conditions in the dark. The more sensitive parasite (the fungus, Metschnikowia ) was damaged even under lower ambient light during late fall (November). With this differential sensitivity established, we evaluated links between light environment and natural outbreaks in lakes. Consistent with the incubations, epidemics of the less sensitive parasite (the bacterium, Pasteuria ) started earlier in the fall (under higher ambient light), and both parasites had smaller outbreaks in more transparent lakes. Overall, light environment may impact the timing and size of disease outbreaks. Outbreaks could thus become exacerbated by human activities that darken waters, including lake browning associated with climate change and eutrophication.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Predicting the distribution range of a recently described, habitat specialist bee - Daniel P. Silva; H. Glenn Hall; John S. Ascher (Journal of Insect Conservation, 2020)

Flood hazard assessment from storm tides, rain and sea level rise for a tidal river estuary - P. M. Orton; F. R. Conticello; F. Cioffi; T. M. Hall; N. Georgas; U. Lall; A. F. Blumberg; K. MacManus (Natural Hazards, 2020)

Correction to: Towards a Better Understanding of Cognitive Deficits in Absence Epilepsy: a Systematic Review and Meta-Analysis - Eric L. A. Fonseca Wald; Jos G. M. Hendriksen; Gerald S. Drenthen; Sander M. J. V. Kuijk; Albert P. Aldenkamp; Johan S. H. Vles; R. Jeroen Vermeulen; Mariette H. J. A. Debeij van Hall; Sylvia Klinkenberg (Neuropsychology Review, 2020)
Due to an error during the editorial phase, a correction regarding Fig. 2 is added to the original article: “Towards a Better Understanding of Cognitive Deficits in Absence Epilepsy: a Systematic Review and Meta-Analysis”. Please see below correct Fig. 2.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Towards a Better Understanding of Cognitive Deficits in Absence Epilepsy: a Systematic Review and Meta-Analysis - Eric L. A. Fonseca Wald; Jos G. M. Hendriksen; Gerald S. Drenthen; Sander M. J. V. Kuijk; Albert P. Aldenkamp; Johan S. H. Vles; R. Jeroen Vermeulen; Mariette H. J. A. Debeij-van Hall; Sylvia Klinkenberg (Neuropsychology Review, 2019)
Cognition in absence epilepsy (AE) is generally considered undisturbed. However, reports on cognitive deficits in AE in recent years have suggested otherwise. This review systematically assesses current literature on cognitive performance in children with AE. A systematic literature search was performed in Pubmed, Embase, Cochrane and Web of Science. All studies reporting on cognitive performance in children with AE were considered. In total 33 studies were eligible for inclusion. Neuropsychological tests were classified into the following domains: intelligence; executive function; attention; language; motor & sensory-perceptual examinations; visuoperceptual/visuospatial/visuoconstructional function; memory and learning; achievement. Random-effect meta-analyses were conducted by estimating the pooled mean and/or pooling the mean difference in case-control studies. Full-scale IQ in children with AE was estimated at 96.78 (95%CI:94.46–99.10) across all available studies and in case-control studies IQ was on average 8.03 (95%CI:-10.45- -5.61) lower. Verbal IQ was estimated at 97.98 (95%CI:95.80–100.16) for all studies and 9.01 (95%CI:12.11- -5.90) points lower in case-control studies. Performance IQ was estimated at 97.23 (93.24–101.22) for all available studies and 5.32 (95%CI:-8.27–2.36) points lower in case-control studies. Lower performance was most often reported in executive function (cognitive flexibility, planning, and verbal fluency) and attention (sustained, selective and divided attention). Reports on school difficulties, neurodevelopmental problems, and attentional problems were high. In conclusion, in contrast to common beliefs, lower than average neurocognitive performance was noted in multiple cognitive domains, which may influence academic and psychosocial development.

Automated lifespan determination across Caenorhabditis strains and species reveals assay-specific effects of chemical interventions - Stephen A. Banse; Mark Lucanic; Christine A. Sedore; Anna L. Coleman-Hulbert; W. Todd Plummer; Esteban Chen; Jason L. Kish; David Hall; Brian Onken; Michael P. Presley; E. Grace Jones; Benjamin W. Blue; et al. (GeroScience, 2019)
The goal of the Caenorhabditis Intervention Testing Program is to identify robust and reproducible pro-longevity interventions that are efficacious across genetically diverse cohorts in the Caenorhabditis genus. The project design features multiple experimental replicates collected by three different laboratories. Our initial effort employed fully manual survival assays. With an interest in increasing throughput, we explored automation with flatbed scanner-based Automated Lifespan Machines (ALMs). We used ALMs to measure survivorship of 22 Caenorhabditis strains spanning three species. Additionally, we tested five chemicals that we previously found extended lifespan in manual assays. Overall, we found similar sources of variation among trials for the ALM and our previous manual assays, verifying reproducibility of outcome. Survival assessment was generally consistent between the manual and the ALM assays, although we did observe radically contrasting results for certain compound interventions. We found that particular lifespan outcome differences could be attributed to protocol elements such as enhanced light exposure of specific compounds in the ALM, underscoring that differences in technical details can influence outcomes and therefore interpretation. Overall, we demonstrate that the ALMs effectively reproduce a large, conventionally scored dataset from a diverse test set, independently validating ALMs as a robust and reproducible approach toward aging-intervention screening.

A Growth and Yield Model for Eucalyptus benthamii in the Southeastern United States - Kevin B Hall; Jl Stape; Bronson P Bullock; Doug Frederick; Jeff Wright; Henrique F Scolforo; Rachel Cook (Forest Science, 2019)
In recent Eucalyptus cold-tolerance trials, E. benthamii has shown good growth rates as well as cold tolerance for USDA Plant Hardiness Zones 8 and 9. This study developed growth and yield models for E. benthamii in the southeastern United States. A network of 182 temporary sample plots of E. benthamii ranging in age from 1.5 to 13.3 years was established, and inventory data were collected. Site quality was determined by fitting a polymorphic site index curve, whereas a function for stand basal area based on age, dominant height, and site occupancy was fitted. Stand-level volume and dry-weight biomass prediction equations were fitted as a function of dominant height and basal area. Based on the growth and yield model results, mean annual increments ranged from 26.4 m3 ha–1 year–1 at rotation age 6 years on the best sites to 13.7 m3 ha–1 year–1 at rotation age 10 years on the poorest sites. This is the first published set of management-oriented models for land managers considering planting E. benthamii in the southeastern United States.

Spatial memory shapes migration and its benefits: evidence from a large herbivore - Jerod A. Merkle; Hall Sawyer; Kevin L. Monteith; Samantha P. H. Dwinnell; Gary L. Fralick; Matthew J. Kauffman (Ecology Letters, 2019)
From fine‐scale foraging to broad‐scale migration, animal movement is shaped by the distribution of resources. There is mounting evidence, however, that learning and memory also guide movement. Although migratory mammals commonly track resource waves, how resource tracking and memory guide long‐distance migration has not been reconciled. We examined these hypotheses using movement data from four populations of migratory mule deer ( n = 91). Spatial memory had an extraordinary influence on migration, affecting movement 2–28 times more strongly than tracking spring green‐up or autumn snow depth. Importantly, with only an ability to track resources, simulated deer were unable to recreate empirical migratory routes. In contrast, simulated deer with memory of empirical routes used those routes and obtained higher foraging benefits. For migratory terrestrial mammals, spatial memory provides knowledge of where seasonal ranges and migratory routes exist, whereas resource tracking determines when to beneficially move within those areas.

Seasonal changes in basking shark vertical space use in the north-east Atlantic - P. D. Doherty; J. M. Baxter; B. J. Godley; R. T. Graham; G. Hall; J. Hall; L. A. Hawkes; S. M. Henderson; L. Johnson; C. Speedie; M. J. Witt (Marine Biology, 2019)
Mobile marine species can exhibit vast movements both horizontally and vertically. Spatial analysis of vertical movements may help improve an understanding of the processes that influence space use. Previously, vertical space use of basking sharks ( Cetorhinus maximus ) in the north-east Atlantic described movements largely within waters of the continental shelf during summer and autumn months, with few records of detailed vertical behaviour during winter. We use archival satellite telemetry data from 32 basking sharks (12 females, 6 males, and 14 of unknown sex measuring 4–5 m ( n = 6), 5–6 m ( n = 10), 6–7 m ( n = 7), 7–8 m ( n = 8), and 8–9 m ( n = 1) estimated total length) tracked over 4 years (2012–2015). The satellite tags provided depth and temperature data for a cumulative 4489 days (mean 140 ± 97 days per shark, range 10–292 days) to describe vertical space use and thermal range of basking sharks in the north-east Atlantic. Basking sharks exhibit seasonality in vertical space use, revealing repeated ‘yo-yo’ movement behaviour with periods of occupancy at depths greater than 1000 m in late winter/early spring. Describing seasonal vertical space use in marine megavertebrates can increase knowledge of movements throughout their environment including physiological and morphological constraints to movement, nutrient transfer, and overlap with anthropogenic threats to inform future conservation strategies.

Floral Odors and the Interaction between Pollinating Ceratopogonid Midges and Cacao - Sarah E. J. Arnold; Samantha J. Forbes; David R. Hall; Dudley I. Farman; Puran Bridgemohan; Gustavo R. Spinelli; Daniel P. Bray; Garvin B. Perry; Leroy Grey; Steven R. Belmain; Philip C. Stevenson (Journal of Chemical Ecology, 2019)
Most plant species depend upon insect pollination services, including many cash and subsistence crops. Plants compete to attract those insects using visual cues and floral odor which pollinators associate with a reward. The cacao tree, Theobroma cacao , has a highly specialized floral morphology permitting pollination primarily by Ceratopogonid midges. However, these insects do not depend upon cacao flowers for their life cycle, and can use other sugar sources. To understand how floral cues mediate pollination in cacao we developed a method for rearing Ceratopogonidae through several complete lifecycles to provide material for bioassays. We carried out collection and analysis of cacao floral volatiles, and identified a bouquet made up exclusively of saturated and unsaturated, straight-chain hydrocarbons, which is unusual among floral odors. The most abundant components were tridecane, pentadecane, ( Z )-7-pentadecene and ( Z )-8-heptadecene with a heptadecadiene and heptadecatriene as minor components. We presented adult midges, Forcipomyia sp. (subgen . Forcipomyia ) , Culicoides paraensis and Dasyhelea borgmeieri, with natural and synthetic cacao flower odors in choice assays. Midges showed weak attraction to the complete natural floral odor in the assay, with no significant evidence of interspecific differences. This suggests that cacao floral volatiles play a role in pollinator behavior. Midges were not attracted to a synthetic blend of the above four major components of cacao flower odor, indicating that a more complete blend is required for attraction. Our findings indicate that cacao pollination is likely facilitated by the volatile blend released by flowers, and that the system involves a generalized odor response common to different species of Ceratopogonidae.

Identification of Female Sex Pheromone for Monitoring the Barred Tooth Striped Moth, Trichopteryx polycommata, a Priority Conservation Species - Ashen Oleander; David R. Hall; Daniel P. Bray; Joseph P. J. Burman (Journal of Chemical Ecology, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Enhancement of primary production during drought in a temperate watershed is greater in larger rivers than headwater streams - J. D. Hosen; K. S. Aho; A. P. Appling; E. C. Creech; J. H. Fair; R. O. Hall; E. D. Kyzivat; R. S. Lowenthal; S. Matt; J. Morrison; J. E. Saiers; J. B. Shanley; et al. (Limnology and Oceanography, 2019)
Drought is common in rivers, yet how this disturbance regulates metabolic activity across network scales is largely unknown. Drought often lowers gross primary production (GPP) and ecosystem respiration (ER) in small headwaters but by contrast can enhance GPP and cause algal blooms in downstream estuaries. We estimated ecosystem metabolism across a nested network of 13 reaches from headwaters to the main stem of the Connecticut River from 2015 through 2017, which encompassed a pronounced drought. During drought, GPP and ER increased, but with greater enhancement in larger rivers. Responses of GPP and ER were partially due to warmer temperatures associated with drought, particularly in the larger rivers where temperatures during summer drought were > 10°C higher than typical summer baseflow. The larger rivers also had low canopy cover, which allowed primary producers to take advantage of lower turbidity and fewer cloudy days during drought. We conclude that GPP is enhanced by higher temperature, lower turbidity, and longer water residence times that are all a function of low discharge, but ecosystem response in temperate watersheds to these drivers depends on light availability regulated by riparian canopy cover. In larger rivers, GPP increased more than ER during drought, even leading to temporary autotrophy, an otherwise rare event in the typically light‐limited heterotrophic Connecticut River main stem. With climate change, rivers and streams may become warmer and drought frequency and severity may increase. Such changes may increase autotrophy in rivers with broad implications for carbon cycling and water quality in aquatic ecosystems.

Effects of Ocean Acidification on Marine Photosynthetic Organisms Under the Concurrent Influences of Warming, UV Radiation, and Deoxygenation - Kunshan Gao; John Beardall; Donat-P. Häder; Jason M. Hall-Spencer; Guang Gao; David A. Hutchins (Frontiers in Marine Science, 2019)

The relationship between forest cover and diet quality: a case study of rural southern Malawi - C. Hall; J. I. Macdiarmid; R. B. Matthews; P. Smith; S. F. Hubbard; T. P. Dawson (Food Security, 2019)

Streamflow regimes and geologic conditions are more important than water temperature when projecting future crayfish distributions - Kevin P. Krause; Huicheng Chien; Darren L. Ficklin; Damon M. Hall; Guenter A. Schuster; Todd M. Swannack; Chris A. Taylor; Jason H. Knouft (Climatic Change, 2019)

Securing a Just Space for Small-Scale Fisheries in the Blue Economy - Philippa J. Cohen; Edward H. Allison; Neil L. Andrew; Joshua Cinner; Louisa S. Evans; Michael Fabinyi; Len R. Garces; Stephen J. Hall; Christina C. Hicks; Terry P. Hughes; Svein Jentoft; David J. Mills; et al. (Frontiers in Marine Science, 2019)

Rising Sea Levels: Helping Decision-Makers Confront the Inevitable - John A. Hall; Christopher P. Weaver; Jayantha Obeysekera; Mark Crowell; Radley M. Horton; Robert E. Kopp; John Marburger; Douglas C. Marcy; Adam Parris; William V. Sweet; William C. Veatch; Kathleen D. White (Coastal Management, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Outlier SNPs detect weak regional structure against a background of genetic homogeneity in the Eastern Rock Lobster, Sagmariasus verreauxi - Laura N. Woodings; Nicholas P. Murphy; Stephen R. Doyle; Nathan E. Hall; Andrew J. Robinson; Geoffrey W. Liggins; Bridget S. Green; Ira R. Cooke; James J. Bell; Jan M. Strugnell (Marine Biology, 2018)

Identification and feld evaluation of female sex pheromone of leaf-eating caterpillar, Opisina arenosella (Lepidoptera: Oecophoridae) - K. R. M. Bhanu; D. R. Hall; R. V. Awalekar; M. Chandrashekharaiah; T. N. Divya; M. S. Prabhakara; K. P. Jayanth (International Journal of Tropical Insect Science, 2018)

Using irrigation to kick‐start multiple‐use water services for small‐scale farmers in Malawi: A case study of the Nkhata Bay District - Sam Stedman; Alien Mathews Mnyimbiri; Zinyengo Kawonga; Mphatso Malota; Dalo Njera; Ralph P. Hall; Rochelle H. Holm (Irrigation and Drainage, 2018)
Irrigation schemes are an important part of meeting the national agenda in Malawi, yet the design and management of these schemes have not taken advantage of emerging approaches that could improve their performance. One such idea is the concept of multiple‐use water services (MUS). This case study focuses on rural irrigation systems in the Nkhata Bay District, evaluating system usage, profiles of the irrigators, and barriers to irrigation to identify opportunities to kick‐start MUS using existing organizational structures. Interviews were conducted with 141 respondents from 5 functioning irrigation sections. The study found that there are already systems in place for cooperation, with both the government and communities each contributing to long‐term sustainability. Basic MUS could advance the water–energy–food–health nexus and build more resilient communities. The following recommendations would enable communities and development partners to advance irrigation‐based MUS in Malawi: (i) target long‐established, committed, farmer groups; (ii) provide reliable and sustainable local technologies to lift water; (iii) improve access to markets and inputs to support higher‐value cash crops being grown on irrigated land; (iv) create an overlap between community‐level irrigation and borehole committees, private sectors, local government ministries and development partners. © 2018 John Wiley & Sons, Ltd.

Substrate-Borne Vibration Mediates Intrasexual Agonism in the New Zealand Cook Strait Giant Weta (Deinacrida rugosa) - Daniel R. Howard; Ashley P. Schmidt; Carrie L. Hall; Andrew C. Mason (Journal of Insect Behavior, 2018)

Dissolution: The Achilles’ Heel of the Triton Shell in an Acidifying Ocean - Ben P. Harvey; Sylvain Agostini; Shigeki Wada; Kazuo Inaba; Jason M. Hall-Spencer (Frontiers in Marine Science, 2018)

Factors affecting field performance of pheromone traps for tobacco beetle, Lasioderma serricorne, and tobacco moth, Ephestia elutella - Christos Athanassiou; Daniel P. Bray; David R. Hall; Charles Phillips; Thomas N. Vassilakos (Journal of Pest Science, 2018)

A five-step protocol for estimating forest cover and rate of change in the New York City watershed - Mehmet Yavuz; Myrna H. P. Hall (Environmental Monitoring and Assessment, 2018)

Shifting stream planform state decreases stream productivity yet increases riparian animal production - Michael P. Venarsky; David M. Walters; Robert O. Hall; Bridget Livers; Ellen Wohl (Oecologia, 2018)

Grass diversification in Madagascar: In situ radiation of two large C 3 shade clades and support for a Miocene to Pliocene origin of C 4 grassy biomes - Jan Hackel; Maria S. Vorontsova; Olinirina P. Nanjarisoa; Russell C. Hall; Jacqueline Razanatsoa; Panagiota Malakasi; Guillaume Besnard (Journal of Biogeography, 2018)
Aim Grasses (Poaceae) are found in all major habitats of Madagascar and have a particular importance in C 4 grasslands, whose origins are controversial. We aimed to estimate the number, age and origins of endemic grass lineages in the Madagascar region, and to compare the diversification of C 3 and C 4 taxa. Location Madagascar and the surrounding Indian Ocean islands, integrated within a global dataset. Methods We estimated 11 time‐calibrated molecular phylogenies including 73% of Madagascar's known grass flora (65% of endemics), using two calibration scenarios. Integrating the available sequences from worldwide grass species, a total of 1928 accessions were analysed. We tested range evolution models, estimated ancestral ranges, and compared the patterns of lineage accumulation between endemic C 3 and C 4 grasses. Results We recovered 69 lineages endemic to or with an estimated origin in the Madagascar region, 25 of them C 3 and 44 C 4 . Range evolution analysis suggests widespread distance‐scaling of dispersal and strongest historical links to Africa. Extant grass diversity largely accumulated since the Miocene, with parallel increases in C 3 and C 4 taxa. Two large C 3 groups in the “Forest shade clade” (Paniceae: Boivinellinae) and the bamboos (subtribe Hickeliinae) have an estimated origin in the Madagascar region. Divergences and crown ages of endemic C 4 lineages largely coincide with the Miocene grassland expansion. Main conclusions Madagascar's extant grass flora is the result of multiple overseas dispersals, predominantly from Africa, and diversified from the Miocene onwards. C 3 grasses are characterized by two large presumed in situ radiations of shade grasses in the Paniceae and bamboos. Endemic C 4 lineages result from twice as many immigration events, resulting in smaller clades. Ages of C 4 lineages are consistent with a Pliocene or Late Miocene origin of grasslands in Madagascar, but estimating the nature and expanse of such early grasslands will require further research.

The metabolic regimes of flowing waters - E. S. Bernhardt; J. B. Heffernan; N. B. Grimm; E. H. Stanley; J. W. Harvey; M. Arroita; A. P. Appling; M. J. Cohen; W. H. McDowell; R. O. Hall; J. S. Read; B. J. Roberts; et al. (Limnology and Oceanography, 2018)
The processes and biomass that characterize any ecosystem are fundamentally constrained by the total amount of energy that is either fixed within or delivered across its boundaries. Ultimately, ecosystems may be understood and classified by their rates of total and net productivity and by the seasonal patterns of photosynthesis and respiration. Such understanding is well developed for terrestrial and lentic ecosystems but our understanding of ecosystem phenology has lagged well behind for rivers. The proliferation of reliable and inexpensive sensors for monitoring dissolved oxygen and carbon dioxide is underpinning a revolution in our understanding of the ecosystem energetics of rivers. Here, we synthesize our current understanding of the drivers and constraints on river metabolism, and set out a research agenda aimed at characterizing, classifying and modeling the current and future metabolic regimes of flowing waters.

Invasion by Rhododendron ponticum depletes the native seed bank with long-term impacts after its removal - Janet E. Maclean; Ruth J. Mitchell; David F. R. P. Burslem; David Genney; Jeanette Hall; Robin J. Pakeman (Biological Invasions, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

Natural acidification changes the timing and rate of succession, alters community structure, and increases homogeneity in marine biofouling communities - Norah E. M. Brown; Marco Milazzo; Samuel P. S. Rastrick; Jason M. Hall‐Spencer; Thomas W. Therriault; Christopher D. G. Harley (Global Change Biology, 2018)
Ocean acidification may have far‐reaching consequences for marine community and ecosystem dynamics, but its full impacts remain poorly understood due to the difficulty of manipulating p CO 2 at the ecosystem level to mimic realistic fluctuations that occur on a number of different timescales. It is especially unclear how quickly communities at various stages of development respond to intermediate‐scale p CO 2 change and, if high p CO 2 is relieved mid‐succession, whether past acidification effects persist, are reversed by alleviation of p CO 2 stress, or are worsened by departures from prior high p CO 2 conditions to which organisms had acclimatized. Here, we used reciprocal transplant experiments along a shallow water volcanic p CO 2 gradient to assess the importance of the timing and duration of high p CO 2 exposure (i.e., discrete events at different stages of successional development vs. continuous exposure) on patterns of colonization and succession in a benthic fouling community. We show that succession at the acidified site was initially delayed (less community change by 8 weeks) but then caught up over the next 4 weeks. These changes in succession led to homogenization of communities maintained in or transplanted to acidified conditions, and altered community structure in ways that reflected both short‐ and longer‐term acidification history. These community shifts are likely a result of interspecific variability in response to increased p CO 2 and changes in species interactions. High p CO 2 altered biofilm development, allowing serpulids to do best at the acidified site by the end of the experiment, although early (pretransplant) negative effects of p CO 2 on recruitment of these worms were still detectable. The ascidians Diplosoma sp. and Botryllus sp. settled later and were more tolerant to acidification. Overall, transient and persistent acidification‐driven changes in the biofouling community, via both past and more recent exposure, could have important implications for ecosystem function and food web dynamics.

Trends in anecdotal fox sightings in Tasmania accounted for by psychological factors - Clive A. Marks; Malcolm Clark; David Obendorf; Graham P. Hall; Inês Soares; Filipe Pereira (Conservation Biology, 2017)
There has been little evaluation of anecdotal sightings as a means to confirm new incursions of invasive species. This paper explores the potential for equivocal information communicated by the media to account for patterns of anecdotal reports. In 2001, it was widely reported that red foxes ( Vulpes vulpes ) had been deliberately released in the island state of Tasmania (Australia), although this claim was later revealed to be baseless. Regardless, by 2013 a total of 3153 anecdotal fox sightings had been reported by members of the public, which implied their distribution was wide. For each month in 2001–2003, we defined a monthly media index (MMI) of fox‐related media coverage, an index of their relative seasonal abundance (abundance), and a factor denoting claims of fox evidence (claimed evidence) regardless of its evidentiary quality. We fitted a generalized linear model with Poisson error for monthly totals of anecdotal sightings with factors of year and claimed evidence and covariates of MMI, abundance, and hours of darkness. The collective effect of psychological factors (MMI, claimed evidence, and year) relative to biophysical factors (photoperiod and abundance) was highly significant (χ 2 = 122.1, df = 6, p p = 0.15). An annual index of fox media from 2001 to 2010 was strongly associated with the yearly tally of anecdotal sightings ( p = 0.018). The odds ratio of sightings ranked as reliable by the fox eradication program in any year decreased exponentially at a rate of 0.00643 as the total number of sightings increased ( p

Cyprinid herpesvirus 3 as a potential biological control agent for carp ( Cyprinus carpio ) in Australia: susceptibility of non‐target species - K A McColl; A Sunarto; J Slater; K Bell; M Asmus; W Fulton; K Hall; P Brown; D Gilligan; J Hoad; L M Williams; M St J Crane (Journal of Fish Diseases, 2017)
Carp ( Cyprinus carpio L.) is a pest species in Australian waterways, and cyprinid herpesvirus 3 (Cy HV ‐3) is being considered as a potential biological control (biocontrol) agent. An important consideration for any such agent is its target specificity. In this study, the susceptibility to Cy HV ‐3 of a range of non‐target species ( NTS ) was tested. The NTS were as follows: 13 native Australian, and one introduced, fish species; a lamprey species; a crustacean; two native amphibian species (tadpole and mature stages); two native reptilian species; chickens; and laboratory mice. Animals were exposed to 100–1000 times the approximate minimum amount of Cy HV ‐3 required to cause disease in carp by intraperitoneal and/or bath challenge, and then examined clinically each day over the course of 28 days post‐challenge. There were no clinical signs, mortalities or histological evidence consistent with a viral infection in a wide taxonomic range of NTS . Furthermore, there was no molecular evidence of infection with Cy HV ‐3, and, in particular, all RT ‐ PCR s for viral mRNA were negative. As a consequence, the results encourage further investigation of Cy HV ‐3 as a potential biocontrol agent that is specific for carp.

Hydrological hazards in Russia: origin, classification, changes and risk assessment - N. L. Frolova; M. B. Kireeva; D. V. Magrickiy; M. B. Bologov; V. N. Kopylov; J. Hall; V. A. Semenov; A. E. Kosolapov; E. V. Dorozhkin; E. A. Korobkina; E. P. Rets; Y. Akutina; et al. (Natural Hazards, 2017)

Novel Bio-Logging Tool for Studying Fine-Scale Behaviors of Marine Turtles in Response to Sound - Reny B. Tyson; Wendy E. D. Piniak; Camila Domit; David Mann; Michael Hall; Douglas P. Nowacek; Mariana M. P. B. Fuentes (Frontiers in Marine Science, 2017)

Genomic inferences of domestication events are corroborated by written records in Brassica rapa - Xinshuai Qi; Hong An; Aaron P. Ragsdale; Tara E. Hall; Ryan N. Gutenkunst; J. Chris Pires; Michael S. Barker (Molecular Ecology, 2017)
Demographic modelling is often used with population genomic data to infer the relationships and ages among populations. However, relatively few analyses are able to validate these inferences with independent data. Here, we leverage written records that describe distinct Brassica rapa crops to corroborate demographic models of domestication. Brassica rapa crops are renowned for their outstanding morphological diversity, but the relationships and order of domestication remain unclear. We generated genomewide SNP s from 126 accessions collected globally using high‐throughput transcriptome data. Analyses of more than 31,000 SNP s across the B. rapa genome revealed evidence for five distinct genetic groups and supported a European–Central Asian origin of B. rapa crops. Our results supported the traditionally recognized South Asian and East Asian B. rapa groups with evidence that pak choi, Chinese cabbage and yellow sarson are likely monophyletic groups. In contrast, the oil‐type B. rapa subsp. oleifera and brown sarson were polyphyletic. We also found no evidence to support the contention that rapini is the wild type or the earliest domesticated subspecies of B. rapa . Demographic analyses suggested that B. rapa was introduced to Asia 2,400–4,100 years ago, and that Chinese cabbage originated 1,200–2,100 years ago via admixture of pak choi and European–Central Asian B. rapa . We also inferred significantly different levels of founder effect among the B. rapa subspecies. Written records from antiquity that document these crops are consistent with these inferences. The concordance between our age estimates of domestication events with historical records provides unique support for our demographic inferences.

Conflicting selection alters the trajectory of molecular evolution in a tripartite bacteria–plasmid–phage interaction - Ellie Harrison; James P. J. Hall; Steve Paterson; Andrew J. Spiers; Michael A. Brockhurst (Molecular Ecology, 2017)
Bacteria engage in a complex network of ecological interactions, which includes mobile genetic elements ( MGE s) such as phages and plasmids. These elements play a key role in microbial communities as vectors of horizontal gene transfer but can also be important sources of selection for their bacterial hosts. In natural communities, bacteria are likely to encounter multiple MGE s simultaneously and conflicting selection among MGE s could alter the bacterial evolutionary response to each MGE . Here, we test the effect of interactions with multiple MGE s on bacterial molecular evolution in the tripartite interaction between the bacterium, Pseudomonas fluorescens , the lytic bacteriophage, SBW 25φ2, and conjugative plasmid, pQBR 103, using genome sequencing of experimentally evolved bacteria. We show that individually, both plasmids and phages impose selection leading to bacterial evolutionary responses that are distinct from bacterial populations evolving without MGE s, but that together, plasmids and phages impose conflicting selection on bacteria, constraining the evolutionary responses observed in pairwise interactions. Our findings highlight the likely difficulties of predicting evolutionary responses to multiple selective pressures from the observed evolutionary responses to each selective pressure alone. Understanding evolution in complex microbial communities comprising many species and MGE s will require that we go beyond studies of pairwise interactions.

Sublethal effects of angling and release on golden perch Macquaria ambigua : implications for reproduction and fish health - K. C. Hall; M. K. Broadhurst; P. A. Butcher; L. Cameron; S. J. Rowland; R. B. Millar (Journal of Fish Biology, 2017)
The present study tested the hypothesis of no delayed sublethal effects of mild angling and release on the feeding, growth, somatic condition and gonadal development of golden perch Macquaria ambigua during gametogenesis. Subsamples of adult M. ambigua ( n = 17–21 of 207), originally captured from the wild and stocked into ten 0·1 ha earthen ponds, were angled and released during early and late gametogenesis. Wild samples that were concurrently collected throughout the experiment underwent rapid and synchronous gonadal development and many spawned. While no spawning occurred in the ponds, most M. ambigua underwent normal gonadal development to maturity, including the angled fish. Angled fish also fed, maintained condition and actually grew faster than non‐angled captive controls. Although females that were angled during late gametogenesis more readily ingested and retained baited hooks, neither their subsequent condition nor gonadal development was significantly affected. The predominance of null results was attributed to the combined effects of the flexible reproductive strategy of M. ambigua , the benignness of mouth hooking and immediate release, and possible methodological issues arising from differential hooking success of more aggressive and resilient individuals. The findings support earlier catch‐and‐release research, but contrast with reports of acute reproductive effects following capture and handling for aquaculture broodstock. This discrepancy highlights the need for research to specifically address welfare questions relevant to recreational fisheries across various species and angling scenarios.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Epipodial Tentacle Gene Expression and Predetermined Resilience to Summer Mortality in the Commercially Important Greenlip Abalone, Haliotis laevigata - Brett P. Shiel; Nathan E. Hall; Ira R. Cooke; Nicholas A. Robinson; Jan M. Strugnell (Marine Biotechnology, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Odorant receptors and antennal lobe morphology offer a new approach to understanding olfaction in the Asian longhorned beetle - Robert F. Mitchell; Loyal P. Hall; Peter F. Reagel; Duane D. McKenna; Thomas C. Baker; John G. Hildebrand (Journal of Comparative Physiology A, 2017)

Digging Deep: Managing Social and Policy Dimensions of Geoduck Aquaculture Conflict in Puget Sound, Washington - C. M. Ryan; P. S. McDonald; D. S. Feinberg; L. W. Hall; J. G. Hamerly; C. W. Wright (Coastal Management, 2017)

Temporal and spatial dynamics of a “Rust-Belt” urban stream: Metabolic and water quality responses to hardened land - K. E. Limburg; D. P. Swaney; M. H. Hall (Urban Ecosystems, 2016)

Evaluating Immunogenicity Risk Due to Host Cell Protein Impurities in Antibody-Based Biotherapeutics - Vibha Jawa; Marisa K. Joubert; Qingchun Zhang; Meghana Deshpande; Suminda Hapuarachchi; Michael P. Hall; Gregory C. Flynn (The AAPS Journal, 2016)

Outlier SNPs enable food traceability of the southern rock lobster, Jasus edwardsii - Cecilia Villacorta-Rath; Irina Ilyushkina; Jan M. Strugnell; Bridget S. Green; Nicholas P. Murphy; Stephen R. Doyle; Nathan E. Hall; Andrew J. Robinson; James J. Bell (Marine Biology, 2016)

Potential effect of atmospheric warming on grapevine phenology and post-harvest heat accumulation across a range of climates - Andrew Hall; Adam J. Mathews; Bruno P. Holzapfel (International Journal of Biometeorology, 2016)

Biological characteristics of three co‐occurring species of armorhead from different genera vary markedly from previous results for the Pentacerotidae - P. G. Coulson; N. G. Hall; I. C. Potter (Journal of Fish Biology, 2016)
Biological characteristics of Pentaceropsis recurvirostris , Paristiopterus gallipavo and Parazanclistius hutchinsi were determined from commercial gillnet samples from temperate south‐western Australian coastal waters. Growth zones in otoliths, with more than a few such zones, were readily detectable only after the otoliths had been sectioned. Visual analyses and modelling of the trends in marginal increments on sectioned otoliths demonstrate that these opaque zones are formed annually. Maximum ages of 55, 36 and 49 years, derived for P. recurvirostris , P. gallipavo and P. hutchinsi , respectively, reflect relatively low mortalities. These longevities greatly exceed those estimated, using otoliths, for Pentaceros wheeleri and Pentaceros richardsoni , which belong to the other pentacerotid subfamily. These differences may be due to the counts of ‘daily’ growth zones in sectioned otoliths of P. wheeleri not representing the complete age range of that species and the zones detected in whole otoliths of P. richardsoni not constituting the complete range of annually‐formed zones. Pentaceropsis recurvirostris , P. gallipavo and P. hutchinsi recruited into the fishery in the sampling area as 2–3 year‐old fishes. Pentaceropsis recurvirostris and P. hutchinsi exhibited little or no subsequent growth throughout the remainder of their protracted life, whereas, P. gallipavo continued to grow for c . 5 years and then underwent little further growth. Spawning of P. recurvirostris and P. hutchinsi peaked in the austral winter and autumn, respectively, but in the austral spring and summer with P. gallipavo , which is more typical of temperate species. Although the females of P. gallipavo and P. hutchinsi were mature, this did not apply to a few P. recurvirostris , some of which were >20 years old, implying that any given female of this species does not always spawn every year. Ovarian mass greatly exceeded testis mass, indicative of pair spawning, which is consistent with field observations. In contrast to P. recurvirostris and P. hutchinsi , the sex ratio was heavily biased towards males and the spawning period longer in P. gallipavo , suggesting that selection pressures for spawning success were greater for this latter species.

Bacterial sensing underlies artificial sweetener‐induced growth of gut L actobacillus - Kristian Daly; Alistair C. Darby; Neil Hall; Mark C. Wilkinson; Pisut Pongchaikul; David Bravo; Soraya P. Shirazi‐Beechey (Environmental Microbiology, 2016)
Summary Disruption in stable establishment of commensal gut microbiota by early weaning is an important factor in susceptibility of young animals to enteric disorders. The artificial sweetener SUCRAM [consisting of neohesperidin dihydrochalcone ( NHDC ) and saccharin] included in piglets' feed reduces incidence of enteric disease. Pyrosequencing of pig caecal 16S r RNA gene amplicons identified 25 major families encompassing seven bacterial classes with B acteroidia , C lostridia and B acilli dominating the microbiota. There were significant shifts in microbial composition in pigs maintained on a diet containing SUCRAM , establishing SUCRAM as a major influence driving bacterial community dynamics. The most notable change was a significant increase of Lactobacillaceae population abundance, almost entirely due to a single phylotype, designated L actobacillus 4228. The sweetener‐induced increase in L actobacillaceae was observed in two different breeds of pigs signifying a general effect. We isolated Lactobacillus 4228, sequenced its genome and found it to be related to L actobacillus amylovorus . In vitro analyses of L actobacillus 4228 growth characteristics showed that presence of NHDC significantly reduces the lag phase of growth and enhances expression of specific sugar transporters, independently of NHDC metabolism. This study suggests that sensing of NHDC by a bacterial plasma membrane receptor underlies sweetener‐induced growth of a health promoting gut bacterium.

Rumen Microorganisms Decrease Bioavailability of Inorganic Selenium Supplements - M. L. Galbraith; W. R. Vorachek; C. T. Estill; P. D. Whanger; G. Bobe; T. Z. Davis; J. A. Hall (Biological Trace Element Research, 2016)

Plant nitrogen concentration and isotopic composition in residential lawns across seven US cities - T. L. E. Trammell; D. E. Pataki; J. Cavender-Bares; P. M. Groffman; S. J. Hall; J. B. Heffernan; S. E. Hobbie; J. L. Morse; C. Neill; K. C. Nelson (Oecologia, 2016)

Ecosystem services in managing residential landscapes: priorities, value dimensions, and cross-regional patterns - K. L. Larson; K. C. Nelson; S. R. Samples; S. J. Hall; N. Bettez; J. Cavender-Bares; P. M. Groffman; M. Grove; J. B. Heffernan; S. E. Hobbie; J. Learned; J. L. Morse; et al. (Urban Ecosystems, 2016)

S almonella infection in grey seals ( H alichoerus grypus ), a marine mammal sentinel species: pathogenicity and molecular typing of S almonella strains compared with human and livestock isolates - Johanna L. Baily; Geoffrey Foster; Derek Brown; Nicholas J. Davison; John E. Coia; Eleanor Watson; Romain Pizzi; Kim Willoughby; Ailsa J. Hall; Mark P. Dagleish (Environmental Microbiology, 2016)
Summary Microbial pollution of the marine environment through land–sea transfer of human and livestock pathogens is of concern. S almonella was isolated from rectal swabs of free‐ranging and stranded grey seal pups (21.1%; 37/175) and compared with strains from the same serovars isolated from human clinical cases, livestock, wild mammals and birds in Scotland, UK to characterize possible transmission routes using pulsed‐field gel electrophoresis and multi‐locus variable number of tandem repeat analyses. A higher prevalence of S almonella was found in pups exposed to seawater, suggesting that this may represent a source of this pathogen. S almonella Bovismorbificans was the most common isolate (18.3% pups; 32/175) and was indistinguishable from isolates found in Scottish cattle. S almonella T yphimurium was infrequent (2.3% pups; 4/175), mostly similar to isolates found in garden birds and, in one case, identical to a highly multidrug resistant strain isolated from a human child. S almonella H aifa was rare (1.1% pups; 2/175), but isolates were indistinguishable from that of a human clinical isolate. These results suggest that S . Bovismorbificans may circulate between grey seal and cattle populations and that both S . Typhimurium and S . Haifa isolates are shared with humans, raising concerns of microbial marine pollution.

Effect of Zinc Intake on Growth in Infants: A Meta-analysis - M. Nissensohn; A. Sánchez-Villegas; D. Fuentes Lugo; P. Henríquez Sánchez; J. Doreste Alonso; L. Peña Quintana; C. Ruano; N. L. Lowe; V. Hall Moran; A. L. Skinner; M. Warthon-Medina; L. Serra-Majem (Critical Reviews in Food Science and Nutrition, 2016)

The variation of crustal stretching and different modes of rifting along the Australian southern continental margin - N. Kharazizadeh; W. P. Schellart; J. C. Duarte; M. Hall (Australian Journal of Earth Sciences, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Photosynthetic innovation broadens the niche within a single species - Marjorie R. Lundgren; Guillaume Besnard; Brad S. Ripley; Caroline E. R. Lehmann; David S. Chatelet; Ralf G. Kynast; Mary Namaganda; Maria S. Vorontsova; Russell C. Hall; John Elia; Colin P. Osborne; Pascal‐Antoine Christin (Ecology Letters, 2015)
Adaptation to changing environments often requires novel traits, but how such traits directly affect the ecological niche remains poorly understood. Multiple plant lineages have evolved C 4 photosynthesis, a combination of anatomical and biochemical novelties predicted to increase productivity in warm and arid conditions. Here, we infer the dispersal history across geographical and environmental space in the only known species with both C 4 and non‐C 4 genotypes, the grass Alloteropsis semialata . While non‐C 4 individuals remained confined to a limited geographic area and restricted ecological conditions, C 4 individuals dispersed across three continents and into an expanded range of environments, encompassing the ancestral one. This first intraspecific investigation of C 4 evolutionary ecology shows that, in otherwise similar plants, C 4 photosynthesis does not shift the ecological niche, but broadens it, allowing dispersal into diverse conditions and over long distances. Over macroevolutionary timescales, this immediate effect can be blurred by subsequent specialisation towards more extreme niches.

Changing gears during succession: shifting functional strategies in young tropical secondary forests - Dylan Craven; Jefferson S. Hall; Graeme P. Berlyn; Mark S. Ashton; Michiel van Breugel (Oecologia, 2015)

Detecting emerald ash borers (Agrilus planipennis) using branch traps baited with 3D-printed beetle decoys - Michael J. Domingue; Drew P. Pulsifer; Akhlesh Lakhtakia; Jennifer Berkebile; Kim C. Steiner; Jonathan P. Lelito; Loyal P. Hall; Thomas C. Baker (Journal of Pest Science, 2015)

Erratum to: Breast cancer screening of underserved women in the USA: results from the National Breast and Cervical Cancer Early Detection Program, 1998–2012 - David H. Howard; Florence K. L. Tangka; Janet Royalty; Lucinda P. Dalzell; Jacqueline Miller; Brett O’Hara; Kristy Joseph; Kristy Kenney; Gery Guy; Ingrid J. Hall (Cancer Causes & Control, 2015)

Erratum to: The reach and health impacts of the National Breast and Cervical Cancer Early Detection Program - Gery P. Guy; Florence K. L. Tangka; Ingrid J. Hall; Jacqueline W. Miller; Janet Royalty (Cancer Causes & Control, 2015)

Erratum to: Cervical cancer screening of underserved women in the United States: results from the National Breast and Cervical Cancer Early Detection Program, 1997–2012 - Florence K. L. Tangka; David H. Howard; Janet Royalty; Lucinda P. Dalzell; Jacqueline Miller; Brett J. O’Hara; Susan A. Sabatino; Kristy Joseph; Kristy Kenney; Gery P. Guy; Ingrid J. Hall (Cancer Causes & Control, 2015)

The Reach and Health Impacts of the National Breast and Cervical Cancer Early Detection Program - Gery P. Guy; Florence K. L. Tangka; Ingrid J. Hall; Jacqueline W. Miller; Janet Royalty (Cancer Causes & Control, 2015)

Cervical cancer screening of underserved women in the United States: results from the National Breast and Cervical Cancer Early Detection Program, 1997–2012 - Florence K. L. Tangka; David H. Howard; Janet Royalty; Lucinda P. Dalzell; Jacqueline Miller; Brett J. O’Hara; Susan A. Sabatino; Kristy Joseph; Kristy Kenney; Gery P. Guy; Ingrid J. Hall (Cancer Causes & Control, 2015)

Breast cancer screening of underserved women in the USA: results from the National Breast and Cervical Cancer Early Detection Program, 1998–2012 - David H. Howard; Florence K. L. Tangka; Janet Royalty; Lucinda P. Dalzell; Jacqueline Miller; Brett O’Hara; Kristy Joseph; Kristy Kenney; Gery Guy; Ingrid J. Hall (Cancer Causes & Control, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

De Novo Characterisation of the Greenlip Abalone Transcriptome (Haliotis laevigata) with a Focus on the Heat Shock Protein 70 (HSP70) Family - Brett P. Shiel; Nathan E. Hall; Ira R. Cooke; Nicholas A. Robinson; Jan M. Strugnell (Marine Biotechnology, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Fragmented Tasmania: the transition from Rodinia to Gondwana - D. H. Moore; P. G. Betts; M. Hall (Australian Journal of Earth Sciences, 2015)

Evidence of land‐sea transfer of the zoonotic pathogen Campylobacter to a wildlife marine sentinel species - Johanna L. Baily; Guillaume Méric; Sion Bayliss; Geoffrey Foster; Simon E. Moss; Eleanor Watson; Ben Pascoe; Jane Mikhail; Romain Pizzi; Robert J. Goldstone; David G. E. Smith; Kim Willoughby; et al. (Molecular Ecology, 2015)
Environmental pollution often accompanies the expansion and urbanization of human populations where sewage and wastewaters commonly have an impact on the marine environments. Here, we explored the potential for faecal bacterial pathogens, of anthropic origin, to spread to marine wildlife in coastal areas. The common zoonotic bacterium Campylobacter was isolated from grey seals ( Halichoerus grypus ), an important sentinel species for environmental pollution, and compared to isolates from wild birds, agricultural sources and clinical samples to characterize possible transmission routes. Campylobacter jejuni was present in half of all grey seal pups sampled (24/50 dead and 46/90 live pups) in the breeding colony on the Isle of May (Scotland), where it was frequently associated with histological evidence of disease. Returning yearling animals (19/19) were negative for C . jejuni suggesting clearance of infection while away from the localized colony infection source. The genomes of 90 isolates from seals were sequenced and characterized using a whole‐genome multilocus sequence typing ( MLST ) approach and compared to 192 published genomes from multiple sources using population genetic approaches and a probabilistic genetic attribution model to infer the source of infection from MLST data. The strong genotype‐host association has enabled the application of source attribution models in epidemiological studies of human campylobacteriosis, and here assignment analyses consistently grouped seal isolates with those from human clinical samples. These findings are consistent with either a common infection source or direct transmission of human campylobacter to grey seals, raising concerns about the spread of human pathogens to wildlife marine sentinel species in coastal areas.

Scaling categorical spatial data for earth systems models - Jaclyn M. Hall; Caroline G. Staub; Matthew P. Marsik; Forrest R. Stevens; Michael W. Binford (Global Change Biology, 2015)

Ocean acidification through the lens of ecological theory - Brian Gaylord; Kristy J. Kroeker; Jennifer M. Sunday; Kathryn M. Anderson; James P. Barry; Norah E. Brown; Sean D Connell; Sam Dupont; Katharina E. Fabricius; Jason M. Hall-Spencer; Terrie Klinger; Marco Milazzo; et al. (Ecology, 2015)
Ocean acidification, chemical changes to the carbonate system of seawater, is emerging as a key environmental challenge accompanying global warming and other human‐induced perturbations. Considerable research seeks to define the scope and character of potential outcomes from this phenomenon, but a crucial impediment persists. Ecological theory, despite its power and utility, has been only peripherally applied to the problem. Here we sketch in broad strokes several areas where fundamental principles of ecology have the capacity to generate insight into ocean acidification's consequences. We focus on conceptual models that, when considered in the context of acidification, yield explicit predictions regarding a spectrum of population‐ and community‐level effects, from narrowing of species ranges and shifts in patterns of demographic connectivity, to modified consumer–resource relationships, to ascendance of weedy taxa and loss of species diversity. Although our coverage represents only a small fraction of the breadth of possible insights achievable from the application of theory, our hope is that this initial foray will spur expanded efforts to blend experiments with theoretical approaches. The result promises to be a deeper and more nuanced understanding of ocean acidification and the ecological changes it portends.

Population genomics of the killer whale indicates ecotype evolution in sympatry involving both selection and drift - Andre E. Moura; John G. Kenny; Roy Chaudhuri; Margaret A. Hughes; Andreanna J. Welch; Ryan R. Reisinger; P. J. Nico de Bruyn; Marilyn E. Dahlheim; Neil Hall; A. Rus Hoelzel (Molecular Ecology, 2014)
The evolution of diversity in the marine ecosystem is poorly understood, given the relatively high potential for connectivity, especially for highly mobile species such as whales and dolphins. The killer whale ( Orcinus orca ) has a worldwide distribution, and individual social groups travel over a wide geographic range. Even so, regional populations have been shown to be genetically differentiated, including among different foraging specialists (ecotypes) in sympatry. Given the strong matrifocal social structure of this species together with strong resource specializations, understanding the process of differentiation will require an understanding of the relative importance of both genetic drift and local adaptation. Here we provide a high‐resolution analysis based on nuclear single‐nucleotide polymorphic markers and inference about differentiation at both neutral loci and those potentially under selection. We find that all population comparisons, within or among foraging ecotypes, show significant differentiation, including populations in parapatry and sympatry. Loci putatively under selection show a different pattern of structure compared to neutral loci and are associated with gene ontology terms reflecting physiologically relevant functions (e.g. related to digestion). The pattern of differentiation for one ecotype in the North Pacific suggests local adaptation and shows some fixed differences among sympatric ecotypes. We suggest that differential habitat use and resource specializations have promoted sufficient isolation to allow differential evolution at neutral and functional loci, but that the process is recent and dependent on both selection and drift.

Seaweed chemical diversity: an additional and efficient tool for coastal evaluation - Cintia D. L. Martins; Cintia Lhullier; Fernanda Ramlov; José Carlos Simonassi; Lidiane P. Gouvea; Mauricio Noernberg; Marcelo Maraschin; Pio Colepicolo; Jason M. Hall-Spencer; Paulo A. Horta (Journal of Applied Phycology, 2014)

Prior infections are associated with increased mortality from subsequent blood-stream infections among patients with hematological malignancies - J. A. Greenberg; M. Z. David; D. L. Pitrak; J. B. Hall; J. P. Kress (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Establishment and Short-term Productivity of Annual and Perennial Bioenergy Crops Across a Landscape Gradient - Danielle M. Wilson; Emily A. Heaton; Lisa A. Schulte; Theodore P. Gunther; Monika E. Shea; Richard B. Hall; William Landon Headlee; Kenneth J. Moore; Nicholas N. Boersma (BioEnergy Research, 2014)

How reliable are crop production data? Case studies in USA and Argentina - V. O. Sadras; P. Grassini; R. Costa; L. Cohan; A. J. Hall (Food Security, 2014)

Convergent Surface Water Distributions in U.S. Cities - M. K. Steele; J. B. Heffernan; N. Bettez; J. Cavender-Bares; P. M. Groffman; J. M. Grove; S. Hall; S. E. Hobbie; K. Larson; J. L. Morse; C. Neill; K. C. Nelson; et al. (Ecosystems, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Infectious disease in consumer populations: dynamic consequences of resource-mediated transmission and infectiousness - Paul J. Hurtado; Spencer R. Hall; Stephen P. Ellner (Theoretical Ecology, 2014)

Clinical signs of barotrauma in golden perch, M acquaria ambigua ( R ichardson), and associated effects on post‐release mortality and health - K C Hall; M K Broadhurst; P A Butcher (Journal of Fish Diseases, 2014)
This study assessed the effects of different retrieval depths (2, 10 or 20 m), surface intervals (none or 15 min) and release methods (untreated, vented or recompressed) on the incidence of external and internal clinical signs of barotrauma ( ECSB and ICSB ) and post‐release mortality in golden perch, Macquaria ambigua (Richardson). Fish were assessed for ECSB before and after surface intervals and either monitored for mortality over 3 days in two deep cages or killed for internal examination. When all fish were left untreated, short‐term mortality increased with retrieval depth from 0% and 4.2% among 2 and 10‐m fish, respectively, to 19.2% among 20‐m fish; while surface interval only affected the incidence of two ECSB (excess buoyancy and a prolapsed cloaca). Mortality was also greater among 20‐m fish that were subjected to a 15‐min surface interval and left untreated (22.2%) or vented (22.2%) than those that were recompressed (5.6%). Of the ECSB , only exophthalmia was associated with increased mortality, with half of the affected fish dying. However, many fish retrieved from 10 and 20 m also sustained numerous ICSB , including compressed gonads or vital organs and ruptured or collapsed, haemorrhaging swimbladders that remained deflated for up to 3 days after release.

Sclerochronological studies reveal that patterns of otolith growth of adults of two co-occurring species of Platycephalidae are synchronised by water temperature variations - P. G. Coulson; B. A. Black; I. C. Potter; N. G. Hall (Marine Biology, 2014)

Vascular biomechanical properties in mice with smooth muscle specific deletion of Ndst1 - Neeta Adhikari; Marie Billaud; Marjorie Carlson; Spencer P. Lake; Kim Ramil C. Montaniel; Rod Staggs; Weihua Guan; Dinesha Walek; Snider Desir; Brant E. Isakson; Victor H. Barocas; Jennifer L. Hall (Molecular and Cellular Biochemistry, 2014)

Biology of the harlequin fish Othos dentex (Serranidae), with particular emphasis on sexual pattern and other reproductive characteristics - B. French; I. C. Potter; S. A. Hesp; P. G. Coulson; N. G. Hall (Journal of Fish Biology, 2014)
Key biological characteristics of the harlequin fish Othos dentex , a representative of a monospecific genus of the Anthiinae (Serranidae), were determined from samples collected around reefs on the south coast of Western Australia. The females of this relatively long‐lived species (maximum recorded age in this study = 37 years) attained only a slightly greater maximum total length and age than males and neither the length nor the age‐frequency distributions showed a conspicuous sex‐based bimodality. Furthermore, gonads from a wide size and age range of O. dentex were shown by histology, at several locations along their length, to always comprise exclusively either ovarian or testicular tissues. Thus, O. dentex is a gonochorist, a sexual pattern only previously recorded definitively for one other anthiine serranid, i.e. Epinephelides armatus , which also occurs in south‐western Australia. Similar to E. armatus , O. dentex possesses ‘solid’ testes with a central sperm duct, thereby differing in structure from those typically found in serranids, in which there is a central membrane‐bound ‘ovarian’ lumen and peripherally located sperm sinuses. The gonadal characteristics and sexual pattern of these two gonochoristic anthiines are not consistent with a recent proposal for the trends exhibited by the evolution of gonochorism and protogyny within the Serranidae. Othos dentex has indeterminate fecundity and a protracted spawning period (7 months) and, on the basis of underwater observations and a low gonado‐somatic index ( I G ) for males, is a pair spawner, which is unusual for a gonochorist of a serranid or member of a related family. While the large spots on the lower half of the body of O. dentex are shown quantitatively to be similarly yellow in juveniles and adult females, they then become blue in males at maturity and this intensifies during the spawning period, when they presumably play an important role in agonistic interactions among males and courtship with females. The attainment of maturity and rapid growth by O. dentex early in life may reflect selection pressures to reduce predation mortality during that period. Total mortality in the population is moderately low during later life, implying that the current fishing pressure on O. dentex is relatively light.

Assessing the sensitivity of habitats to fishing: from seabed maps to sensitivity maps a - N. C. Eno; C. L. J. Frid; K. Hall; K. Ramsay; R. A. M. Sharp; D. P. Brazier; S. Hearn; K. M. Dernie; K. A. Robinson; O. A. L. Paramor; L. A. Robinson (Journal of Fish Biology, 2013)
In the Welsh part of the Irish Sea, a method was developed for assessing the sensitivity of different seabed habitats to existing fishing activities, across a range of potential fishing intensities. The resistance of 31 habitats and their associated biological assemblage to damage by 14 categories of fishing activity were assessed along with the rate at which each habitat would recover following impact (resilience). Sensitivity was scored based on a combination of the resistance of a habitat to damage and its subsequent rate of recovery. The assessments were based, wherever possible, on scientific literature, with expert judgement used to extrapolate results to habitat and gear combinations not directly examined in the published literature. The resulting sensitivity matrices were then subject to further peer review at a series of workshops. Following consensus on the habitat sensitivity, these data were combined with the most resolved sea‐floor habitat maps. These habitat sensitivity maps can help inform the development of site‐specific management plans, as well as having a place in spatial planning and aiding managers in developing dialogue with other stakeholders. A case study of their application is provided.

Causes and methods to estimate cryptic sources of fishing mortality a - E. Gilman; P. Suuronen; M. Hall; S. Kennelly (Journal of Fish Biology, 2013)
Cryptic, not readily detectable, components of fishing mortality are not routinely accounted for in fisheries management because of a lack of adequate data, and for some components, a lack of accurate estimation methods. Cryptic fishing mortalities can cause adverse ecological effects, are a source of wastage, reduce the sustainability of fishery resources and, when unaccounted for, can cause errors in stock assessments and population models. Sources of cryptic fishing mortality are (1) pre‐catch losses, where catch dies from the fishing operation but is not brought onboard when the gear is retrieved, (2) ghost‐fishing mortality by fishing gear that was abandoned, lost or discarded, (3) post‐release mortality of catch that is retrieved and then released alive but later dies as a result of stress and injury sustained from the fishing interaction, (4) collateral mortalities indirectly caused by various ecological effects of fishing and (5) losses due to synergistic effects of multiple interacting sources of stress and injury from fishing operations, or from cumulative stress and injury caused by repeated sub‐lethal interactions with fishing operations. To fill a gap in international guidance on best practices, causes and methods for estimating each component of cryptic fishing mortality are described, and considerations for their effective application are identified. Research priorities to fill gaps in understanding the causes and estimating cryptic mortality are highlighted.

Differences in the antibiotic susceptibility of human Escherichia coli with poultry-associated and non-poultry-associated extended-spectrum beta-lactamases - T. N. Platteel; M. A. Leverstein-Van Hall; J. W. Cohen Stuart; G. M. Voets; M. P. Munckhof; J. Scharringa; N. Sande; A. C. Fluit; M. J. M. Bonten (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Reliability of individual and pooled test procedures for detecting the pathogenic agent for clinical infectious salmon anaemia - M Hall; I S Wallace; L A Munro; E S Munro; R McIntosh; P Cook; C E T Allan; A G Murray (Journal of Fish Diseases, 2013)

Linking anti‐predator behaviour to prey demography reveals limited risk effects of an actively hunting large carnivore - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; Michael D. Jimenez; Rachel C. Cook; John G. Cook; Shannon E. Albeke; Hall Sawyer; P. J. White (Ecology Letters, 2013)
Ecological theory predicts that the diffuse risk cues generated by wide‐ranging, active predators should induce prey behavioural responses but not major, population‐ or community‐level consequences. We evaluated the non‐consumptive effects ( NCE s) of an active predator, the grey wolf ( Canis lupus ), by simultaneously tracking wolves and the behaviour, body fat, and pregnancy of elk ( Cervus elaphus ), their primary prey in the Greater Yellowstone Ecosystem. When wolves approached within 1 km, elk increased their rates of movement, displacement and vigilance. Even in high‐risk areas, however, these encounters occurred only once every 9 days. Ultimately, despite 20‐fold variation in the frequency of encounters between wolves and individual elk, the risk of predation was not associated with elk body fat or pregnancy. Our findings suggest that the ecological consequences of actively hunting large carnivores, such as the wolf, are more likely transmitted by consumptive effects on prey survival than NCE s on prey behaviour.

Whole exome sequencing in dominant cataract identifies a new causative factor, CRYBA2, and a variety of novel alleles in known genes - Linda M. Reis; Rebecca C. Tyler; Sanaa Muheisen; Victor Raggio; Leonardo Salviati; Dennis P. Han; Deborah Costakos; Hagith Yonath; Sarah Hall; Patricia Power; Elena V. Semina (Human Genetics, 2013)

Effects of multiple stressors on lakes in south-central Ontario: 15 years of change in lakewater chemistry and sedimentary diatom assemblages - Kristopher R. Hadley; Andrew M. Paterson; Roland I. Hall; John P. Smol (Aquatic Sciences, 2013)

Water-use efficiency and whole-plant performance of nine tropical tree species at two sites with contrasting water availability in Panama - D. Craven; J. S. Hall; M. S. Ashton; G. P. Berlyn (Trees, 2013)

Approximate B ayesian estimation of extinction rate in the F innish D aphnia magna metapopulation - John D. Robinson; David W. Hall; John P. Wares (Molecular Ecology, 2013)
Approximate B ayesian computation ( ABC ) is useful for parameterizing complex models in population genetics. In this study, ABC was applied to simultaneously estimate parameter values for a model of metapopulation coalescence and test two alternatives to a strict metapopulation model in the well‐studied network of D aphnia magna populations in Finland. The models shared four free parameters: the subpopulation genetic diversity ( θ S ), the rate of gene flow among patches (4 N m ), the founding population size ( N 0 ) and the metapopulation extinction rate ( e ) but differed in the distribution of extinction rates across habitat patches in the system. The three models had either a constant extinction rate in all populations (strict metapopulation), one population that was protected from local extinction ( i.e . a persistent source), or habitat‐specific extinction rates drawn from a distribution with specified mean and variance. Our model selection analysis favoured the model including a persistent source population over the two alternative models. Of the closest 750 000 data sets in E uclidean space, 78% were simulated under the persistent source model (estimated posterior probability = 0.769). This fraction increased to more than 85% when only the closest 150 000 data sets were considered (estimated posterior probability = 0.774). Approximate Bayesian computation was then used to estimate parameter values that might produce the observed set of summary statistics. Our analysis provided posterior distributions for e that included the point estimate obtained from previous data from the F innish D . magna metapopulation. Our results support the use of ABC and population genetic data for testing the strict metapopulation model and parameterizing complex models of demography.

A Male-Predominant Cuticular Hydrocarbon, 7-Methyltricosane, is used as a Contact Pheromone in the Western Flower Thrips Frankliniella occidentalis - Oladele A. Olaniran; Akella V. S. Sudhakar; Falko P. Drijfhout; Ian A. N. Dublon; David R. Hall; James G. C. Hamilton; William D. J. Kirk (Journal of Chemical Ecology, 2013)

Predator guild does not influence orangutan alarm call rates and combinations - Adriano R. Lameira; Han de Vries; Madeleine E. Hardus; Cedric P. A. Hall; Tatang Mitra-Setia; Berry M. Spruijt; Arik Kershenbaum; Elisabeth H. M. Sterck; Maria van Noordwijk; Carel van Schaik; Serge A. Wich (Behavioral Ecology and Sociobiology, 2013)

Disease-Driven Amphibian Declines Alter Ecosystem Processes in a Tropical Stream - M. R. Whiles; R. O. Hall; W. K. Dodds; P. Verburg; A. D. Huryn; C. M. Pringle; K. R. Lips; S. S. Kilham; C. Colón-Gaud; A. T. Rugenski; S. Peterson; S. Connelly (Ecosystems, 2013)

Biosecure packaging for the transport of diagnostic samples - P. Glocke; B. H. Hall (Australasian Plant Pathology, 2012)

Adding pieces to the puzzle: episodic crustal growth and a new terrane in the northeast Yilgarn Craton, Western Australia - M. J. Pawley; M. T. D. Wingate; C. L. Kirkland; S. Wyche; C. E. Hall; S. S. Romano; M. P. Doublier (Australian Journal of Earth Sciences, 2012)

Global habitat suitability of cold‐water octocorals - Chris Yesson; Michelle L. Taylor; Derek P. Tittensor; Andrew J. Davies; John Guinotte; Amy Baco; Julie Black; Jason M. Hall‐Spencer; Alex D. Rogers (Journal of Biogeography, 2012)
Aim Three‐quarters of Octocorallia species are found in deep waters. These cold‐water octocoral colonies can form a major constituent of structurally complex habitats. The global distribution and the habitat requirements of deep‐sea octocorals are poorly understood given the expense and difficulties of sampling at depth. Habitat suitability models are useful tools to extrapolate distributions and provide an understanding of ecological requirements. Here, we present global habitat suitability models and distribution maps for seven suborders of Octocorallia: Alcyoniina, Calcaxonia, Holaxonia, Scleraxonia, Sessiliflorae, Stolonifera and Subselliflorae. Location Global. Methods We use maximum entropy modelling to predict octocoral distribution using a database of 12,508 geolocated octocoral specimens and 32 environmental grids resampled to 30 arc‐second (approximately 1 km 2 ) resolution. Additionally, a meta‐analysis determined habitat preferences and niche overlap between the different suborders of octocorals. Results Suborder Sessiliflorae had the widest potential habitat range, but all records for all suborders implied a habitat preference for continental shelves and margins, particularly the North and West Atlantic and Western Pacific Rim. Temperature, salinity, broad scale slope, productivity, oxygen and calcite saturation state were identified as important factors for determining habitat suitability. Less than 3% of octocoral records were found in waters undersaturated for calcite, but this result is affected by a shallow‐water sampling bias. Main conclusions The logistical difficulties, expense and vast areas associated with deep‐sea sampling leads to a gap in the knowledge of faunal distributions that is difficult to fill without predictive modelling. Global distribution estimates are presented, highlighting many suitable areas which have yet to be studied. We suggest that approximately 17% of oceans are suitable for at least one suborder but 3.5% may be suitable for all seven. This is the first global habitat suitability modelling study on the distribution of octocorals and forms a useful resource for researchers, managers and conservationists.

A universal airborne LiDAR approach for tropical forest carbon mapping - Gregory P. Asner; Joseph Mascaro; Helene C. Muller-Landau; Ghislain Vieilledent; Romuald Vaudry; Maminiaina Rasamoelina; Jefferson S. Hall; Michiel van Breugel (Oecologia, 2012)

Resilience of inshore, juvenile snapper Pagrus auratus to angling and release - M. K. Broadhurst; P. A. Butcher; K. C. Hall; B. R. Cullis; S. P. McGrath (Journal of Fish Biology, 2012)
This study assessed the mortality of 157 snapper Pagrus auratus (9–29 cm, total length, L T ) after being conventionally angled and then released into cages (along with 48 controls) for 4 days off south‐eastern Australia. Fatalities were restricted to 12 angled fish (7·6%) and mostly attributed to the ingestion of hooks and especially their subsequent removal, which caused substantial blood loss and immediate death. Hook ingestion was significantly biased towards smaller fish ( L T ) and attributed to a lower chance of anglers initially detecting these individuals on the line (allowing them to consume more of the baits). While mortalities might be reduced in future via (1) choosing terminal rigs that promote mouth hooking and (2) cutting the line on any‐hook ingested fish, the results nevertheless validate releasing unwanted angled inshore juvenile P. auratus as a means for managing their exploitation.

Population genetic diversity and structure of two rare vernal pool grasses in central California - Sarah P. Gordon; Christina M. Sloop; Heather G. Davis; J. Hall Cushman (Conservation Genetics, 2012)

Post‐release mortality of angled golden perch Macquaria ambigua and Murray cod Maccullochella peelii - K. C. HALL; M. K. BROADHURST; P. A. BUTCHER (Fisheries Management and Ecology, 2012)
Short‐term (≤4 days) post‐release mortalities of two large, culturally and ecologically important Australian freshwater teleosts golden perch Macquaria ambigua (Richardson) and Murray cod Maccullochella peelii (Mitchell) were investigated. There was no angler‐induced mortality among golden perch that were immediately released in winter and spring, but 24% of this species and 15% of Murray cod died after delayed release in summer. Significant predictors of mortality were limited to times caught and total length for golden perch, and restraint methods and recovery times for Murray cod, but other parameters were also implicated as cumulative influences. The estimated mortalities may be sufficient to produce population‐level impacts for these two long‐lived species but could be considerably reduced through revisions of tournament regulations.

Foliar herbivory and leaf traits of five native tree species in a young plantation of Central Panama - Gillian S. Paul; Florencia Montagnini; Graeme P. Berlyn; Dylan J. Craven; Michiel van Breugel; Jefferson S. Hall (New Forests, 2012)

Solar radiation decreases parasitism in Daphnia - Erin P. Overholt; Spencer R. Hall; Craig E. Williamson; Claire K. Meikle; Meghan A. Duffy; Carla E. Cáceres (Ecology Letters, 2012)
Ecology Letters (2011) 14 : 47–54 Abstract Climate change and variation in atmospheric ozone are influencing the intensity of ultraviolet radiation (UVR) reaching ecosystems. Changing UVR regimes, in turn, may alter epidemics of infectious disease. This possibility hinges on the sensitivity of epidemiologically relevant traits of host and parasite to UVR. We address this issue using a planktonic system (a zooplankton host, Daphnia dentifera , and its virulent fungal parasite, Metschnikowia bicuspidata ). Controlled laboratory experiments, coupled with in situ field incubations of spores, revealed that quite low levels of UVR (as well as longer wavelength light) sharply reduced the infectivity of fungal spores but did not affect host susceptibility to infection. The parasite’s sensitivity to solar radiation may underlie patterns in a lake survey: higher penetration of solar radiation into lakes correlated with smaller epidemics that started later in autumn (as incident sunlight declined). Thus, solar radiation, by diminishing infectivity of the parasite, may potently reduce disease.

Decomposition of urban atmospheric carbon in Sonoran Desert soils - Jason P. Kaye; Sara E. Eckert; Daniel A. Gonzales; Jonathan O. Allen; Sharon J. Hall; Ryan A. Sponseller; Nancy B. Grimm (Urban Ecosystems, 2011)

Effects of barotrauma and mitigation methods on released Australian bass Macquaria novemaculeata - J. P. Roach; K. C. Hall; M. K. Broadhurst (Journal of Fish Biology, 2011)
The effects of barotrauma on the short‐term mortality and physical condition of Australian bass Macquaria novemaculeata were investigated after being: (1) conventionally angled and released during two tournaments in deep impoundments and (2) released untreated or subjected to venting or recompression during a manipulative experiment. All fish were released into two 20 m deep bathy‐cages and monitored for 3 days. Of 238 M. novemaculeata angled during the tournaments, 43 (18·1%) had clinical signs of barotrauma or were vented and five of these later died (11·6% mortality). Catch histories varied significantly between both barotrauma and non‐barotrauma fish and tournaments, but only hook ingestion significantly influenced mortality ( P M. novemaculeata suffering barotrauma should be immediately released with no treatment. Fish that are unable to resubmerge should be recompressed, while those held in live wells and released in shallow water should be vented.

Capsaicin-induced vasodilatation in human nasal vasculature is mediated by modulation of cyclooxygenase-2 activity and abrogated by sulprostone - Koen Van Crombruggen; L. Van Nassauw; L. Derycke; J.-P. Timmermans; G. Holtappels; D. Hall; C. Bachert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Simian varicella virus open reading frame 63/70 expression is required for efficient virus replication in culture - Elizabeth Brazeau; Mary Wellish; Benedict B. Kaufer; B. Karsten Tischer; Wayne Gray; Fuchun Zhou; Nikolaus Osterrieder; Teri Hanlon; Anjani Golive; Travis Hall; Sreekala Nair; Gregory P. Owens; et al. (Journal of NeuroVirology, 2011)

Genomic variations define divergence of water/wildlife‐associated Campylobacter jejuni niche specialists from common clonal complexes - Philip J. Hepworth; Kevin E. Ashelford; Jason Hinds; Katherine A. Gould; Adam A. Witney; Nicola J. Williams; Howard Leatherbarrow; Nigel P. French; Richard J. Birtles; Chriselle Mendonca; Nick Dorrell; Brendan W. Wren; et al. (Environmental Microbiology, 2011)
Summary Although the major food‐borne pathogen Campylobacter jejuni has been isolated from diverse animal, human and environmental sources, our knowledge of genomic diversity in C. jejuni is based exclusively on human or human food‐chain‐associated isolates. Studies employing multilocus sequence typing have indicated that some clonal complexes are more commonly associated with particular sources. Using comparative genomic hybridization on a collection of 80 isolates representing diverse sources and clonal complexes, we identified a separate clade comprising a group of water/wildlife isolates of C. jejuni with multilocus sequence types uncharacteristic of human food‐chain‐associated isolates. By genome sequencing one representative of this diverse group ( C. jejuni 1336), and a representative of the bank‐vole niche specialist ST‐3704 ( C. jejuni 414), we identified deletions of genomic regions normally carried by human food‐chain‐associated C. jejuni . Several of the deleted regions included genes implicated in chicken colonization or in virulence. Novel genomic insertions contributing to the accessory genomes of strains 1336 and 414 were identified. Comparative analysis using PCR assays indicated that novel regions were common but not ubiquitous among the water/wildlife group of isolates, indicating further genomic diversity among this group, whereas all ST‐3704 isolates carried the same novel accessory regions. While strain 1336 was able to colonize chicks, strain 414 was not, suggesting that regions specifically absent from the genome of strain 414 may play an important role in this common route of Campylobacter infection of humans. We suggest that the genomic divergence observed constitutes evidence of adaptation leading to niche specialization.

Paleoredox status and thermal alteration of the lower Cambrian (Series 2) Emu Bay Shale Lagerstätte, South Australia - D. M. McKirdy; P. A. Hall; C. Nedin; G. P. Halverson†; B. H. Michaelsen; J. B. Jago; J. G. Gehling; R. J. F. Jenkins (Australian Journal of Earth Sciences, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Within-season temporal variation in correlations between vineyard canopy and winegrape composition and yield - Andrew Hall; David W. Lamb; Bruno P. Holzapfel; John P. Louis (Precision Agriculture, 2011)

Biology of Salpa thompsoni in waters adjacent to the Ross Sea, Southern Ocean, during austral summer 2008 - E. A. Pakhomov; J. Hall; M. J. M. Williams; B. P. V. Hunt; C. J. Stevens (Polar Biology, 2011)

Ligand-Binding Mass Spectrometry to Study Biotransformation of Fusion Protein Drugs and Guide Immunoassay Development: Strategic Approach and Application to Peptibodies Targeting the Thrombopoietin Receptor - Michael P. Hall; Colin Gegg; Kenneth Walker; Christopher Spahr; Robert Ortiz; Vimal Patel; Steven Yu; Liana Zhang; Hsieng Lu; Binodh DeSilva; Jean W. Lee (The AAPS Journal, 2010)

Effects of ocean acidification on invertebrate settlement at volcanic CO2 vents - M. Cigliano; M. C. Gambi; R. Rodolfo-Metalpa; F. P. Patti; J. M. Hall-Spencer (Marine Biology, 2010)

Seamounts as refugia from ocean acidification for cold‐water stony corals - Derek P. Tittensor; Amy R. Baco; Jason M. Hall‐Spencer; James C. Orr; Alex D. Rogers (Marine Ecology, 2010)
Cold‐water stony corals create habitat for a diverse range of deep‐water species but are thought to be threatened by ocean acidification due to oceanic uptake of anthropogenic CO 2 . Knowledge of the severity of this threat is hampered by our limited understanding of the distribution and habitat requirements of these corals. Here we estimate the global acidification threat to these organisms using a global database of cold‐water stony coral records and a species distribution modelling approach. We parameterised the models using present‐day environmental data, and then replaced these data with future projections of ocean chemistry from the year 2099. We found suitable coral habitat to be very heterogeneously distributed, being concentrated in the northern North Atlantic and around New Zealand. Projected changes in ocean chemistry induced a pronounced reduction in habitat suitability in the North Atlantic, and a low‐to‐moderate impact elsewhere under both the IPCC IS92a and S650 scenarios. Seamount summits are impacted by these changes, but consistently provide more suitable habitat than the surrounding seafloor, with around 98% of seamount summits having higher suitability in both future scenarios; this is because they lie in shallower waters with a higher aragonite saturation state. These results suggest that anthropogenic‐induced changes in ocean chemistry are likely to severely impact cold‐water stony coral habitat in the deep‐sea of the North Atlantic, and that impacts will be less severe elsewhere. We predict that coral communities on the summits and upper slopes of seamounts will be less susceptible to ocean acidification during this century than those on the surrounding seafloor, and thus that seamounts may serve as temporary refugia.

Sprouty1 inhibits angiogenesis in association with up-regulation of p21 and p27 - Sangjin Lee; Tri M. Bui Nguyen; Dmitry Kovalenko; Neeta Adhikari; Suzanne Grindle; Sean P. Polster; Robert Friesel; Sundaram Ramakrishnan; Jennifer L. Hall (Molecular and Cellular Biochemistry, 2010)

Performance is no proxy for genetic quality: trade‐offs between locomotion, attractiveness, and life history in crickets - Simon P. Lailvaux; Matthew D. Hall; Robert C. Brooks (Ecology, 2010)
The genetic relationships among traits contributing to overall fitness are an important subject of inquiry because such relationships influence how suites of traits respond to selection. Within the field of sexual selection, these relationships are also of interest for assessing whether any given trait can be used as a proxy for total fitness. A growing number of studies have demonstrated close links between whole‐organism performance traits and determinants of individual fitness; however, an understanding of the genetic relationships between performance and important aspects of genetic quality is currently lacking. We present the results of a quantitative genetic study in which we estimate covariation between a locomotor performance trait (maximal jumping ability), calling effort, sexual attractiveness, and life‐history traits in male Teleogryllus commodus crickets. We show that the major axis of genetic variation ( g max ) is characterized by a contrast between jump performance and life‐history traits associated with mating success. Moreover, two additional axes of significant multivariate genetic variation exist, each characterized by strong contrasts among traits. These results argue against the existence of a single axis representing genetic quality, favoring instead the idea that resource allocation strategies shape multiple dimensions of genetic quality through trade‐offs among key life‐history traits, including performance.

Forest structure without ground data: Adaptive Full-Blind Multiple Forward-Mode reflectance model inversion in a mountain pine beetle damaged forest - Derek R. Peddle; Sarah Boon; Aaron P. Glover; Forrest G. Hall (International Journal of Remote Sensing, 2010)

Historical and paleolimnological evidence for expansion of Lake Athabasca (Canada) during the Little Ice Age - R. Niloshini Sinnatamby; Yi Yi; Michael A. Sokal; Kenneth P. Clogg-Wright; Taro Asada; Sheila R. Vardy; Tammy L. Karst-Riddoch; William M. Last; John W. Johnston; Roland I. Hall; Brent B. Wolfe; Thomas W. D. Edwards (Journal of Paleolimnology, 2010)

A multidisciplinary study of archaeological grape seeds - Enrico Cappellini; M. Thomas P. Gilbert; Filippo Geuna; Girolamo Fiorentino; Allan Hall; Jane Thomas-Oates; Peter D. Ashton; David A. Ashford; Paul Arthur; Paula F. Campos; Johan Kool; Eske Willerslev; et al. (The Science of Nature, 2010)

Effects of angling on post‐release mortality, gonadal development and somatic condition of Australian bass Macquaria novemaculeata - K. C. Hall; M. K. Broadhurst; P. A. Butcher; S. J. Rowland (Journal of Fish Biology, 2009)
This study assessed the protracted effects of two angling treatments (mild and harsh) on the post‐release mortality, gonadal development and somatic condition of Australian bass Macquaria novemaculeata in a pond‐based experiment. Angled fish were destructively sampled (along with controls) three times: immediately before, and 1 or 4 weeks after release into cages. Compared with the other groups, harshly angled fish had similar, low immediate and short‐term mortalities (≤5%), but significant delayed mortality (25%) and fed only minimally. None of these fish ejected ingested hooks. Forty‐six per cent of captive fish (across all groups) and 20% of wild fish had non‐ripening gonads (stage I) prior to, or during, the experiment. In females with ripening ovaries (stages II or III), neither angling treatment significantly reduced standardized gonadal mass. The mean per cent of atretic oocytes increased among females in all groups, but was significantly greater in those that were harshly angled. The results demonstrated that the gonadal development of M. novemaculeata could be suppressed or impaired (by angling, handling and confinement), and that further research is warranted. In particular, the timing and severity of angling in relation to the stage of gonadal development could have important implications for the introduction of temporal restrictions to angling.

Sensory Imbalance as Mechanism of Orientation Disruption in the Leafminer Phyllocnistis citrella: Elucidation by Multivariate Geometric Designs and Response Surface Models - Stephen L. Lapointe; Lukasz L. Stelinski; Terence J. Evens; Randall P. Niedz; David G. Hall; Agenor Mafra-Neto (Journal of Chemical Ecology, 2009)

Integrated analysis of risks of coastal flooding and cliff erosion under scenarios of long term change - R. J. Dawson; M. E. Dickson; R. J. Nicholls; J. W. Hall; M. J. A. Walkden; P. K. Stansby; M. Mokrech; J. Richards; J. Zhou; J. Milligan; A. Jordan; S. Pearson; et al. (Climatic Change, 2009)

A novel extended family of stromal thioredoxins - Peter Cain; Michael Hall; Wolfgang P. Schröder; Thomas Kieselbach; Colin Robinson (Plant Molecular Biology, 2009)

Urbanization Alters Soil Microbial Functioning in the Sonoran Desert - S. J. Hall; B. Ahmed; P. Ortiz; R. Davies; R. A. Sponseller; N. B. Grimm (Ecosystems, 2009)

Predicting global habitat suitability for stony corals on seamounts - Derek P. Tittensor; Amy R. Baco; Paul E. Brewin; Malcolm R. Clark; Mireille Consalvey; Jason Hall‐Spencer; Ashley A. Rowden; Thomas Schlacher; Karen I. Stocks; Alex D. Rogers (Journal of Biogeography, 2009)
Aim Globally, species distribution patterns in the deep sea are poorly resolved, with spatial coverage being sparse for most taxa and true absence data missing. Increasing human impacts on deep‐sea ecosystems mean that reaching a better understanding of such patterns is becoming more urgent. Cold‐water stony corals (Order Scleractinia) form structurally complex habitats (dense thickets or reefs) that can support a diversity of other associated fauna. Despite their widely accepted ecological importance, records of scleractinian corals on seamounts are patchy and simply not available for most of the global ocean. The objective of this paper is to model the global distribution of suitable habitat for stony corals on seamounts. Location Seamounts worldwide. Methods We compiled a database containing all accessible records of scleractinian corals on seamounts. Two modelling approaches developed for presence‐only data were used to predict global habitat suitability for seamount scleractinians: maximum entropy modelling (Maxent) and environmental niche factor analysis (ENFA). We generated habitat‐suitability maps and used a cross‐validation process with a threshold‐independent metric to evaluate the performance of the models. Results Both models performed well in cross‐validation, although the Maxent method consistently outperformed ENFA. Highly suitable habitat for seamount stony corals was predicted to occur at most modelled depths in the North Atlantic, and in a circumglobal strip in the Southern Hemisphere between 20° and 50° S and shallower than around 1500 m. Seamount summits in most other regions appeared much less likely to provide suitable habitat, except for small near‐surface patches. The patterns of habitat suitability largely reflect current biogeographical knowledge. Environmental variables positively associated with high predicted habitat suitability included the aragonite saturation state, and oxygen saturation and concentration. By contrast, low levels of dissolved inorganic carbon, nitrate, phosphate and silicate were associated with high predicted suitability. High correlation among variables made assessing individual drivers difficult. Main conclusions Our models predict environmental conditions likely to play a role in determining large‐scale scleractinian coral distributions on seamounts, and provide a baseline scenario on a global scale. These results present a first‐order hypothesis that can be tested by further sampling. Given the high vulnerability of cold‐water corals to human impacts, such predictions are crucial tools in developing worldwide conservation and management strategies for seamount ecosystems.

Short‐term mortality of Australian bass, Macquaria novemaculeata , after catch‐and‐release angling - K. C. HALL; P. A. BUTCHER; M. K. BROADHURST (Fisheries Management and Ecology, 2009)
Australian bass, Macquaria novemaculeata Steindachner, is angled in large numbers from coastal impoundments and rivers throughout south‐eastern Australia. Many are released in the belief that most survive with few negative short‐term impacts. This assumption was investigated in three experiments involving a range of conventional angling scenarios. A total of 313 Australian bass were angled and then released along with appropriate controls into either land‐based tanks or floating cages, where they were monitored for up to 5 days. No controls died. Short‐term mortalities of angled fish were low (0–6%) and attributed to the effects of bait type, hook location and fish size ( P 0.05). Specifically, fish that ingested hooks or were caught with natural baits were more likely to die than those that were mouth‐hooked or caught on lures. Mortality negatively correlated with fish size. The results supported previous assertions that Australian bass is a resilient, hardy species that should tolerate short‐term impacts associated with catch‐and‐release angling. However, other sublethal physiological impacts that could contribute towards delayed mortalities or reduced reproductive output warrant further investigation, particularly in relation to native populations in coastal rivers that form gauntlet fisheries during their annual spawning season.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Professional and personal attitudes of researchers in ageing towards life extension - Mair Underwood; Helen P. Bartlett; Wayne D. Hall (Biogerontology, 2009)

Minimum Flows and Levels Method of the St. Johns River Water Management District, Florida, USA - Clifford P. Neubauer; Greeneville B. Hall; Edgar F. Lowe; C. Price Robison; Richard B. Hupalo; Lawrence W. Keenan (Environmental Management, 2008)

Live imaging early immune cell ontogeny and function in zebrafish Danio rerio - C. J. Hall; M. V. Flores; K. E. Crosier; P. S. Crosier (Journal of Fish Biology, 2008)
The success of a robust vertebrate inflammatory response is in part because of the migratory potential of its haematopoietic components. Once these cells converge at an inflammatory site, they interact with each other as well as non‐immune tissues and infectious agents to help manage both the scale and the duration of any ensuing response. Exactly how these blood cells, that constitute the innate and adaptive immune systems, contribute to such immune responses remain largely unknown. Traditionally, assessing these contributions relied upon histological analysis of fixed tissue sections complemented with in vitro dynamic data. Although informative, translating results from these studies into the multicellular whole‐animal setting remain difficult. Recently, non‐invasive live imaging of the immune system in animal models is providing significant insights into how immune cells function within their intact natural environment. Although the majority of these studies have been conducted within mice, another vertebrate, the zebrafish Danio rerio is being recognized as an ideal platform for non‐invasive live imaging applications. The optical transparency, rapid development, genetic tractability and highly conserved innate and adaptive immune systems of this well‐established developmental model have been exploited in a number of recent studies evaluating the immunocompetence of fluorescently tagged blood cells. In addition, similar live imaging studies are helping to dissect the ontogeny of blood‐cell development by tracking various haematopoietic precursor cells to assess their contribution to different blood lineages. This review will examine some recent advances that have helped D. rerio emerge as a live imaging platform as well as its potential to offer valuable insights into the genetics behind diseases associated with immune cell dysfunction.

Relative Wulst volume is correlated with orbit orientation and binocular visual field in birds - Andrew N. Iwaniuk; Christopher P. Heesy; Margaret I. Hall; Douglas R. W. Wylie (Journal of Comparative Physiology A, 2008)

Climate simulations for 1880–2003 with GISS modelE - J. Hansen; M. Sato; R. Ruedy; P. Kharecha; A. Lacis; R. Miller; L. Nazarenko; K. Lo; G. A. Schmidt; G. Russell; I. Aleinov; S. Bauer; et al. (Climate Dynamics, 2007)

Biological invasion alters regional nitrogen‐oxide emissions from tropical rainforests - SHARON J. HALL; GREGORY P. ASNER (Global Change Biology, 2007)
We explored whether the invasion of an exotic, nitrogen (N) fixing tree into native Hawaiian tropical forests has altered regional emissions of nitrous oxide (N 2 O) and nitric oxide (NO), two atmospherically important trace gases produced by microorganisms in soils. Ecosystem processes, including nitrification and N‐oxide emissions, were not affected by Morella faya (formerly Myrica faya ) invasion until it dominated the community with few native species in the overstory or understory. Remote‐sensing estimates of upper‐canopy leaf N concentration were strongly correlated to N‐oxide emissions in ecosystems at the mesic‐wet end of a precipitation gradient, where temperatures are warm, relatively constant, and N limits biological processes. In contrast, remotely sensed and field‐based canopy chemistry was not related to N‐oxide emissions in dry forest ecosystems where the seasonality of temperature and moisture exerted stronger control over soil gas fluxes. Thus, remote sensing of canopy N was useful for estimating the impact of M. faya on regional N‐oxide emissions only in regions receiving >1800 mm rainfall annually. Our estimates of N‐oxide emissions from M. faya are half as large and 35 times more precise than those made using traditional, plot‐level methods of extrapolation. Over the 40 years since its first occurrence in wet forests of Hawai'i Volcanoes National Park, M. faya has increased N‐oxide emissions 16‐fold, with its effects most pronounced in summer and at the N‐rich centers of dense, monospecific stands.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Delivery of cancer genetics services: The Royal Marsden telephone clinic model - S. Shanley; K. Myhill; R. Doherty; A. Ardern-Jones; S. Hall; C. Vince; S. Thomas; P. Aspinall; R. Eeles (Familial Cancer, 2007)

Hurricane track forecasting with OMEGA - David P. Bacon; Nash′at N. Ahmad; Thomas J. Dunn; S. G. Gopalakrishnan; Mary S. Hall; Ananthakrishna Sarma (Natural Hazards, 2007)

Ethylene Receptors: Ethylene Perception and Signal Transduction - Brenda P. Hall; Samina N. Shakeel; G. Eric Schaller (Journal of Plant Growth Regulation, 2007)

Edwin K. Silverman, Steven D. Shapiro, David A. Lomas, Scott T. Weiss: Respiratory Genetics - Ian P. Hall (Human Genetics, 2007)

Genetic structure of introduced European fallow deer (Dama dama dama) in Tasmania, Australia - Lee S. Webley; Kyall R. Zenger; Graham P. Hall; Desmond W. Cooper (European Journal of Wildlife Research, 2007)

Functional polymorphism and differential regulation of CYSLTR1 transcription in human airway smooth muscle and monocytes - Nathalie P. Duroudier; Ian Sayers; Charlotte Carabott Castagna; Anthony G. Fenech; Eva Halapi; Caroline Swan; Ian P. Hall (Cell Biochemistry and Biophysics, 2007)

Focusing of phytodetritus deposition beneath a deep‐ocean front, Chatham Rise, New Zealand - Scott D. Nodder; Gerard C. A. Duineveld; Conrad A. Pilditch; Philip J. Sutton; P. Keith Probert; Marc S. S. Lavaleye; Rob Witbaard; F. Hoe Chang; Julie A. Hall; Ken M. Richardson (Limnology and Oceanography, 2007)
In October 2001, we observed a deep‐ocean phytodetritus deposition event on Chatham Rise beneath the Subtropical Front (STF). The origin of this phytodetritus was probably an extensive phytoplankton bloom that occurred in the STF in the preceding weeks. We assessed the spatial distribution of the deposition event using video images from benthic lander and epibenthic trawl deployments and sediment pigment analyses at six sites on a north—south transect across Chatham Rise. High surficial sediment chlorophyll a concentrations were restricted spatially to the southern flank of Chatham Rise (350–1,200‐m depth) with the highest values centered at ~750‐m water depth (750 S). This southern 750 S site was also the only site where macroscopic phytodetritus was observed, coincident with elevated benthic biomass and sediment community respiration rates. At 750 S, phytodetritus resuspension was observed on video and corroborated by current meter, sediment trap, and optical backscatter measurements, suggesting a threshold erosion current speed for phytodetritus of ~10 cm s −1 , equivalent to a shear velocity of 0.5 cm s −1 and similar to other deep‐ocean studies elsewhere. The restriction of macroscopic phytodetritus deposition to 750 S was related to a zone of current convergence within the STF and lower near‐bed current speeds observed across ~1‐day that promoted deposition. Observations of high benthic biomass and respiration on the southern flank of Chatham Rise suggest that this focusing process is important in fueling the energy demands of benthic communities, in association with the general west‐east advection of organic matter within the STF itself. Such physical focusing of labile organic matter deposition may be an important process in other highly productive frontal systems.

Genetic variation at the growth hormone (GH1) and growth hormone receptor (GHR) loci as a risk factor for hypertension and stroke - Martin Horan; Vicky Newsway; Yasmin; Mark D. Lewis; Tammy E. Easter; D. Aled Rees; Arti Mahto; David S. Millar; Annie M. Procter; Maurice F. Scanlon; Ian B. Wilkinson; Ian P. Hall; et al. (Human Genetics, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Chondroid bone and secondary cartilage contribute to apical dentary growth in juvenile Atlantic salmon - J. A. Gillis; P. E. Witten; B. K. Hall (Journal of Fish Biology, 2006)
The microstructure and tissue composition of the dentary bone in Atlantic salmon salmo salar parr were examined using a variety of histological and whole‐mount techniques. Proximally, the dentary is composed of typical cellular lamellar bone with Sharpey's fibres extending dorsally, proximally and ventrally. Meckel's cartilage is located medially through the entire length of the dentary, and degrades distally resulting in a short transitional zone between hyaline cartilage and connective tissue. At the distal tip of the dentary, isogenic clusters of chondrocytes of periosteal origin were observed secreting small amounts of pericellular cartilage matrix within the bone matrix. These characteristics are highly indicative of secondary chondrogenesis, and suggest that the apical part of the dentary bone in Atlantic salmon does not grow via ‘pure’ intramembranous ossification, but rather via a modified mode of periosteal ossification involving secondary cartilage and chondroid bone. Furthermore, the unusual mode of gender‐related dentary growth (kype formation) in adult male Atlantic salmon could be the continuation of a general mode of salmonid apical dentary growth.

Identification of Components of Male-Produced Pheromone of Coffee White Stemborer, Xylotrechus quadripes - D. R. Hall; A. Cork; S. J. Phythian; S. Chittamuru; B. K. Jayarama; M. G. Venkatesha; K. Sreedharan; P. K. Vinod Kumar; H. G. Seetharama; R. Naidu (Journal of Chemical Ecology, 2006)

Predicting Species Response to Disturbance from Size Class Distributions of Adults and Saplings in a Jamaican Tropical Dry Forest - K. P. McLaren; M. A. McDonald; J. B. Hall; J. R. Healey (Plant Ecology, 2005)

Attraction of Male European Tarnished Plant Bug, Lygus rugulipennis to Components of the Female Sex Pheromone in the Field - P. J. Innocenzi; D. Hall; J. V. Cross; H. Hesketh (Journal of Chemical Ecology, 2005)

Organization, not duplication, triggers silencing in a complex transgene locus in rice - Guojun Yang; Yeon-Hee Lee; Yiming Jiang; Siva P. Kumpatla; Timothy C. Hall (Plant Molecular Biology, 2005)

Distribution and toxicity of a new colonial Microcystis aeruginosa bloom in the San Francisco Bay Estuary, California - P. W. Lehman; G. Boyer; C. Hall; S. Waller; K. Gehrts (Hydrobiologia, 2005)

A new approach to the solution of the linear mixing model for a single isotope: application to the case of an opportunistic predator - S. A. Hall-Aspland; A. P. Hall; T. L. Rogers (Oecologia, 2005)

Investigation of Long-Range Female Sex Pheromone of the European Tarnished Plant Bug, Lygus rugulipennis: Chemical, Electrophysiological, and Field Studies - P. J. Innocenzi; D. R. Hall; J. V. Cross; H. Masuh; S. J. Phythian; S. Chittamaru; S. Guarino (Journal of Chemical Ecology, 2004)

Tidal currents, energy flux and bottom boundary layer thickness in the Clyde Sea and North Channel of the Irish Sea - A. M. Davies; P. Hall; M. J. Howarth; P. J. Knight; R. J. Player (Ocean Dynamics, 2004)

Molecular Characterization of Duck Hepatitis B Virus Isolates from South African Ducks - Nomathibane P. Mangisa; Heidi E. Smuts; Anna Kramvis; C. Wendy Linley; Michelle Skelton; Timothy J. Tucker; Pauline De La M. Hall; Del Kahn; Allison R. Jilbert; Michael C. Kew (Virus Genes, 2004)

Molecular and morphological analyses of the cuttlefish Sepia apama indicate a complex population structure - K. S. Kassahn; S. C. Donnellan; A. J. Fowler; K. C. Hall; M. Adams; P. W. Shaw (Marine Biology, 2003)

The cellular distribution and oxidation state of platinum(II) and platinum(IV) antitumour complexes in cancer cells - Matthew D. Hall; Carolyn T. Dillon; Mei Zhang; Philip Beale; Zhonghou Cai; Barry Lai; Anton P. J. Stampfl; Trevor W. Hambley (JBIC Journal of Biological Inorganic Chemistry, 2003)

Thidiazuron induces shoot organogenesis at low concentrations and somatic embryogenesis at high concentrations on leaf and petiole explants of African violet (Saintpaulia ionantha Wendl.) - J. Mithila; J. Hall; J.M.R. Victor; P. Saxena (Plant Cell Reports, 2003)

Development of a Provisional Physical Habitat Index for Maryland Freshwater Streams - Lenwood W. Hall; Raymond P. Morgan; Elgin S. Perry; Anita Waltz (Environmental Monitoring and Assessment, 2002)

Global Distribution of Halogenated Dimethyl Bipyrroles in Marine Mammal Blubber - S. Tittlemier; A. Borrell; J. Duffe; P. J. Duignan; P. Fair; A. Hall; P. Hoekstra; K. M. Kovacs; M. M. Krahn; M. Lebeuf; C. Lydersen; D. Muir; et al. (Archives of Environmental Contamination and Toxicology, 2002)

5-Lipoxygenase polymorphism and in-vivo response to leukotriene receptor antagonists - Stephen J. Fowler; Ian P. Hall; Andrew M. Wilson; Amanda P. Wheatley; Brian J. Lipworth (European Journal of Clinical Pharmacology, 2002)

Adrenocortical responsiveness in southern elephant seal mothers and pups during lactation and the effect of scientific handling - Engelhard G.; Brasseur S.; Hall A.; Burton H.; Reijnders P. (Journal of Comparative Physiology B, 2002)

USE OF MIDAZOLAM/PETHIDINE AND TILETAMINE/ZOLAZEPAM COMBINATIONS FOR THE CHEMICAL RESTRAINT OF LEOPARD SEALS ( HYDRURGA LEPTONYX ) - Damien P. Higgins; Tracey L. Rogers; Andrew D. Irvine; Sophie A. Hall‐Aspland (Marine Mammal Science, 2002)
A bstract We immobilized 200–550‐kg leopard seals ( Hydrurga leptonyx ) on sea ice in Prydz Bay, Antarctica (68°25′S, 77°10′E) between November 1997 and February 2000. Midazolam (0.18–0.27 mg/kg)/ pethidine (1.0–1.5 mg/kg) was administered by dart to 16 leopard seals. Unpredictable immobilization, poor airway maintenance, and our inability to fully assess the suitability of flumazenil (0.003–0.01 mg/kg), naloxone (0.01–0.013 mg/kg), and naltrexone (0.05–0.12 mg/kg) as reversal agents limited suitability of midazolam/pethidine. Tiletamine/zolazepam 1:1 (0.5–1.5 mg/kg) was, therefore, administered to 19 leopard seals. It produced faster induction (19 ± 3 min), more effective and reliable response to dose (rank correlation: r s = 0.88, n = 18), and better pulmonary ventilation and faster return of cognitive function upon recovery, in comparison to midazolam/pethidine. Best results were achieved with tiletamine/zolazepam (1.2–1.4 mg/kg) which safely immobilized seven of nine seals for 20–30 min. Entry to the water upon darting was minimized, but not eliminated, by the use of lightweight air‐pressurized darts and a thorough knowledge of leopard seal behavior.

In Vivo Lung Deposition of Hollow Porous Particles from a Pressurized Metered Dose Inhaler - Peter H. Hirst; Gary R. Pitcairn; Jeff G. Weers; Thomas E. Tarara; Andrew R. Clark; Luis A. Dellamary; Gail Hall; Jolene Shorr; Stephen P. Newman (Pharmaceutical Research, 2002)

Landscape effects of climate, agriculture, and urbanization on benthic invertebrate communities of Canadian prairie lakes - Roberto Quinlan; Peter R. Leavitt; Aruna S. Dixit; Roland I. Hall; John P. Smol (Limnology and Oceanography, 2002)
Paleoecological analyses of fossil chironomid assemblages from eight lakes of the Qu'Appelle Valley, Saskatchewan, Canada, were used to quantify the relative influence of climate, resource use, and urbanization on benthic invertebrate communities 1850–1995. Fossil analyses inferred that Qu'Appelle lakes are naturally productive but that invertebrate communities were altered by agriculture and urbanization. In western lakes, rates of community change (chord distance per 5 yr) were low and nonsignificant (P Cladotanytarsus mancus group, Tanytarsus s.lat. [s.l.]). Comparison of historical and fossil time series (~1920–1993) using variance partitioning analysis (VPA) explained up to 86.6% of past variations in chironomid community composition. Unexpectedly, climate (winter temperature) explained a significant (P , 0.05) and substantial (mean ± SD, n =5 8; 24.8 ± 21.9%) amount of community variance at all sites except Round Lake. In contrast, land‐use practices exhibited significant but less substantial (6.7 ± 6.1%, n = 8) impacts on zoobenthos of five lakes, whereas significant urban impacts (3.6 ± 7.5%, n = 8) were recorded only at two sites. Similarly, redundancy analysis showed that minimum winter or spring temperature significantly influenced the relative abundance of littoral taxa in seven lakes. Such strong effects of climate on benthic invertebrate communities contrast its weak effects on phytoplankton in these lakes and suggest that future environmental change may be expressed differentially among habitats.

Visualisation of metal deposition in biofilm reactors by three-dimensional magnetic resonance imaging (MRI) - Kevin P. Nott; M. Paterson-Beedle; Lynne E. Macaskie; Laurance D. Hall (Biotechnology Letters, 2001)

Vastus medialis muscle oxygenation trends during a simulated 20-km cycle time trial - J. P. Neary; K. Hall; Y. N. Bhambhani (European Journal of Applied Physiology, 2001)

Relationships between land use and stream invertebrate community structure in a South Island, New Zealand, coastal stream catchment - Matthew J. Hall; Gerard P. Closs; Ralph H. Riley (New Zealand Journal of Marine and Freshwater Research, 2001)
Macroinvertebrate community composition was compared across streams draining catchments dominated by either native bush, agricultural or urban land uses within the Water of Leith stream catchment near Dunedin, New Zealand. Land use was associated with differences in taxon richness and faunal composition of communities present in each stream. The mean abundance levels of Ephemeroptera, Plecoptera, and Trichoptera were highest in native bush catchments, and lowest in urban catchments. In contrast, the mean abundance of Oligochaeta exhibited the opposite pattern. Increasing dominance of the urban and agricultural streams by pollution tolerant taxa was reflected in the Macroinvertebrate Community Index and Quantitative Macroinvertebrate Community Index scores.

Components of Male Aggregation Pheromone of Strawberry Blossom Weevil, Anthonomus rubi Herbst. (Coleoptera: Curculionidae) - P. J. Innocenzi; D. R. Hall; J. V. Cross (Journal of Chemical Ecology, 2001)

Chromatin structure and phaseolin gene regulation - Guofu Li; Mahesh B. Chandrasekharan; Alan P. Wolffe; Timothy C. Hall (Plant Molecular Biology, 2001)

Status of biological control by egg parasitoids of Diaprepes abbreviatus (Coleoptera: Curculionidae) in citrus in Florida and Puerto Rico - D.G. Hall; J. Peña; R. Franqui; R. Nguyen; P. Stansly; C. McCoy; S.L. Lapointe; R.C. Adair; B. Bullock (BioControl, 2001)

A high-resolution record of mire development and climatic change spanning the Late-glacial-Holocene boundary at Church Moss, Davenham (Cheshire, England) - P. D. M. Hughes; H. K. Kenward; A. R. Hall; F. D. Large (Journal of Quaternary Science, 2000)

PCR rescue and analysis of transgene sequences directly from crude extracts of transgenic embryos and plants - C. M. Higgins; R. M. Hall; P. R. Campbell; R. G. Dietzgen (Plant Molecular Biology Reporter, 2000)

Transgene silencing in monocots - Lakshminarayan M. Iyer; Siva P. Kumpatla; Mahesh B. Chandrasekharan; Timothy C. Hall (Plant Molecular Biology, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

A theory for the membrane potential of living cells - L. P. Endresen; K. Hall; J. S. Høye; J. Myrheim (European Biophysics Journal, 2000)

Density–dependent recruitment of Puntius sophore in floodplain waterbodies in Bangladesh - A. S. Halls; K. Debnath†; G. P. Kirkwood; A. I. Payne (Journal of Fish Biology, 2000)
Recruitment of Puntius sophore in floodplain waters of Bangladesh was strongly densitydependent at a range of high stock densities and can be described by a Ricker model. Recruitment at low stock density was correlated strongly with waterbody fertility measured in terms of nitrate concentration. The implications of these results are discussed in terms of community–based management.

Z-IQNP: a potential radioligand for SPECT imaging of muscarinic acetylcholine receptors in Alzheimer's disease - K. Nobuhara; C. Halldin; H. Hall; P. Karlsson; L. Farde; J. Hiltunen; D. W. McPherson; A. Savonen; K. A. Bergström; S. Pauli; C.-G. Swahn; S. A. Larsson; et al. (Psychopharmacology, 2000)

Quantitative inferences of past hypolimnetic anoxia and nutrient levels from a Canadan Precambrian Shield lake - Saloni Clerk; Roland Hall; Roberto Quinlan; John P. Smol (Journal of Paleolimnology, 2000)

The Forest Bank ™: An Experiment in Managing Fragmented Forests - Jason P. Dedrick; Troy E. Hall; R. Bruce Hull IV; James E. Johnson (Journal of Forestry, 2000)
As the trend toward smaller parcels of land continues, many of the values associated with forestland are at risk. The Forest Bank ™, an ecosystem-based approach to forest management on private lands in southwestern Virginia, points to a potential new direction in forest management. Sponsored by The Nature Conservancy, this program attempts to blend economic and ecological objectives into an effort that will appeal to private landowners.

Immunohistochemical identification of a vacuolar proton pump (V‐ATPase) in bone‐resorbing cells of an advanced teleost species, Oreochromis niloticus - P. E. Witten; L. S. Holliday; G. Delling; B. K. Hall (Journal of Fish Biology, 1999)
Poly‐and monoclonal antibodies, raised against mammalian membrane‐bound proton pump (V‐ATPase) were applied to the bone‐resorbing cells of Oreochromis niloticus to clarify if osteoclasts of an advanced teleost species display V‐ATPase, a key enzyme in the process of bone resorption. All antibodies labelled cells at known sites of bone resorption, the endosteal bone surfaces surrounding the tooth anlagen. The best results were achieved with a monoclonal antibody (E11). Although the majority of labelled cells were flat and mononucleated, the occurrence of V‐ATPase in these cells indicates that they function as active bone‐resorbing cells. The monoclonal antibody E11 was also applied successfully to monocytes, cells that are believed to be related most closely to osteoclasts. The assignment of V‐ATPase to boneresorbing cells of O. niloticus was confirmed by application of the additional osteoclast markers, tartrate‐resistant acid phosphatase (TRAP) and tartrate‐resistant ATPase (TraATPase). Co‐expression of V‐ATPase, TRAP and TraATPase in fish osteoclasts is demonstrated for the first time.

Concurrent Exposure Assessments of Atrazine and Metolachlor in the Mainstem, Major Tributaries and Small Streams of the Chesapeake Bay Watershed: Indicators of Ecological Risk - Lenwood W. Hall; Ronald D. Anderson; Jay Kilian; Dennis P. Tierney (Environmental Monitoring and Assessment, 1999)

Chrysophyte cysts as paleolimnological indicators of environmental change due to cottage development and acidic deposition in the Muskoka-Haliburton region, Ontario, Canada - Anna N. Wilkinson; Roland I. Hall; John P. Smol (Journal of Paleolimnology, 1999)

Unprecedented Low Levels of Genetic Variation and Inbreeding Depression in an Island Population of the Black‐Footed Rock‐Wallaby - Mark D. B. Eldridge; Juliet M. King; Anne K. Loupis; Peter B. S. Spencer; Andrea C. Taylor; Lisa C. Pope; Graham P. Hall (Conservation Biology, 1999)
It has been argued that demographic and environmental factors will cause small, isolated populations to become extinct before genetic factors have a significant negative impact. Islands provide an ideal opportunity to test this hypothesis because they often support small, isolated populations that are highly vulnerable to extinction. To assess the potential negative impact of isolation and small population size, we compared levels of genetic variation and fitness in island and mainland populations of the black‐footed rock‐wallaby ( Petrogale lateralis [Marsupialia: Macropodidae]). Our results indicate that the Barrow Island population of P. lateralis has unprecedented low levels of genetic variation ( H e = 0.053, from 10 microsatellite loci) and suffers from inbreeding depression (reduced female fecundity, skewed sex ratio, increased levels of fluctuating asymmetry). Despite a long period of isolation ( ∼ 1600 generations) and small effective population size ( N e ∼ 15), demographic and environmental factors have not yet driven this population to extinction. Nevertheless, it has been affected significantly by genetic factors. It has lost most of its genetic variation and become highly inbred ( F e = 0.91), and it exhibits reduced fitness. Because several other island populations of P. lateralis also exhibit exceptionally low levels of genetic variation, this phenomenon may be widespread. Inbreeding in these populations is at a level associated with high rates of extinction in populations of domestic and laboratory species. Genetic factors cannot then be excluded as contributing to the extinction proneness of small, isolated populations.

Glucose, and not sucrose, is transported from wheat to wheat powdery mildew - P. N. Sutton; M. J. Henry; J. L. Hall (Planta, 1999)

Comparibility of Results Obtained by the Use of Different Selective Extraction Schemer for the Determination of Element Forms in Soils - G. E. M. Hall; P. Pelchat (Water, Air, & Soil Pollution, 1999)

Effects of agriculture, urbanization, and climate on water quality in the northernGreat Plains - Roland I. Hall; Peter R. Leavitt; Roberto Quinlan; Aruna S. Dixit; John P. Smol (Limnology and Oceanography, 1999)
The Qu'Appelle Valley drainage system provides water to a third of the population of the Canadian Great Plains, yet is plagued by poor water quality, excess plant growth, and periodic fish kills. Fossil algae (diatoms, pigments) and invertebrates (chironomids) in Pasqua Lake were analyzed by variance partitioning analysis (VPA) to determine the relative importance of climate, resource use, and urbanization as controls of aquatic community composition 1920‐1994. From fossil analyses, we identified three distinct biological assemblages in Pasqua Lake. Prior to agriculture (ca. 1776‐1890), the lake was naturally eutrophic with abundant cyanobacterial carotenoids (myxo‐xanthophyll, aphanizophyll), eutrophic diatoms ( Stephanodiscus niagarae , Aulacoseira granulata , Fragilaria capucina / bidens ), and anoxia‐tolerant chironomids ( Chironomus ). Principal components (PCA) and dissimilarity analyses demonstrated that diatom and chironomid communities did not vary significantly ( P > 0.05) before European settlement. Communities changed rapidly during early land settlement (ca. 1890‐1930) before forming a distinct assemblage ca. 1930–1960 characterized by elevated algal biomass (inferred as β‐carotene), nuisance cyanobacteria, eutrophic Stephanodiscus hantzschii , and low abundance of deep‐water zoobenthos. Recent fossil assemblages (1977–1994) were variable and indicated water quality had not improved despite 3‐fold reduction in phosphorus from sewage. Comparison of fossil community change and continuous annual records of 83 environmental variables (1890–1994) using VPA captured 71–97% of variance in fossil composition using only 10‐14 significant factors. Resource use (cropland area, livestock biomass) and urbanization (nitrogen in sewage) were stronger determinants of algal and chironomid community change than were climatic factors (temperature, evaporation, river discharge). Landscape analysis of inferred changes in past algal abundance (as β‐carotene; ca. 1780‐1994) indicated that urban impacts declined with distance from point sources and suggested that management strategies will vary with lake position within the catchment.

Algal responses to dissolved organic carbon loss and pH decline during whole‐lakeacidification: Evidence from paleolimnology - P. R. Leavitt; D. L. Findlay; R. I. Hall; J. P. Smol (Limnology and Oceanography, 1999)
Fossil pigment analyses and 19 year‐long historical records were used to quantify whole‐lake algal response to changes in optical and chemical properties following experimental acidification of Lake 302 with H 2 SO 4 (south basin, 302S; 1981—1989) or HNO 3 (north basin, 302N; 1982–1986) and HCl (1987–1989). Undisturbed sediments were collected by freeze‐coring, sectioned in approximately annual intervals, and analyzed for fossil carotenoids, chlorophylls, and derivatives by high performance liquid chromatography. Concentrations of fucoxanthin (diatoms, chrysophytes, some dinoflagellates) were correlated with algal standing crop ( r 2 = 0.67, P 2 SO 4 from pH 6.6 to 5.0, consistent with observed reductions in dissolved organic carbon (DOC) from 7 to 4.5 mg liter −1 , improved water clarity, and increased biomass of deep‐water chrysophytes. However, fucoxanthin concentrations declined to baseline values in sediments from 1988 to 1990, concomitant with severe acidification to pH 4.5, continued DOC loss ( −1 ) and an estimated 8‐fold increase in the penetration of UVb radiation (UVR‐b). Increased penetration of ultraviolet radiation (UVR) was recorded also by increased relative abundance of pigments characteristic of UVR‐transparent environments. In contrast, pigments from green algae (Chl b , pheophytin b , lutein‐zeaxanthin) doubled during acidification with H 2 SO 4 , while those from cryptophytes (alloxanthin) were unaffected and diatoxanthin from diatoms declined. Patterns of ubiquitous β‐carotene, Chl a , and pheophytin a suggested that total algal biomass increased ∼200–400% by the mid‐1980s, but declined to near‐baseline under severe acidification. Variance partitioning using redundancy analysis captured 80–83% of variation in fossil chlorophylls and carotenoids and suggested that the direct effects of pH were greater (~50% of total variance) than those of irradiance (~12%), but that ∼20% of variance was attributable to factor interactions. Fossil concentrations of pigments from green algae and diatoms increased ~100% following acidification of Lake 302N to pH 6.1, but there were few signals of deep‐water blooms, possibly because DOC remained 3.5–5.0 mg liter −1 . Such complex interactions between pH, DOC, and light may help explain the high variability of algal biomass response to lake acidification.

Development of a Mercury Vapour Air Analyser for Measurement of Hg in Solution - G. E. M. Hall; P. Pelchat (Water, Air, & Soil Pollution, 1999)

Specificity of Response to Sex Pheromones Among Sweetpotato Weevils, Cylas puncticollis and C. brunneus - M. C. A. Downham; N. E. J. M. Smit; P. O. Laboke; D. R. Hall; D. I. Farman; A. Braun; B. Odongo (Journal of Chemical Ecology, 1999)

Longevity of 5-azacytidine-mediated gene expression and re-establishment of silencing in transgenic rice - Siva P. Kumpatla; Timothy C. Hall (Plant Molecular Biology, 1998)

Late Holocene eruptive activity at Nevado Cayambe Volcano, Ecuador - P. Samaniego; M. Monzier; C. Robin; M. L. Hall (Bulletin of Volcanology, 1998)

Maryland Biological Stream Survey: Development of a Fish Index of Biotic Integrity - N. Roth; M. Southerland; J. Chaillou; R. Klauda; P. Kazyak; S. Stranko; S. Weisberg; L. Hall; R. Morgan II (Environmental Monitoring and Assessment, 1998)

Effect of oral creatine ingestion on parameters of the work rate-time relationship and time to exhaustion in high-intensity cycling - Jimmy C. Smith; Daniel P. Stephens; Emily L. Hall; Allen W. Jackson; Conrad P. Earnest (European Journal of Applied Physiology, 1998)

Cardiorespiratory responses to underwater treadmill walking in healthy females - J. Hall; I. A. Macdonald; P. J. Maddison; J. P. O'Hare (European Journal of Applied Physiology, 1998)

A genetic linkage map of cowpea (Vigna unguiculata) developed from a cross between two inbred, domesticated lines - C. M. Menéndez; A. E. Hall; P. Gepts (Theoretical and Applied Genetics, 1997)

Food as the Dominant Pathway of Methylmercury Uptake by Fish - B. D. Hall; R. A. Bodaly; R. J. P. Fudge; J. W. M. Rudd; D. M. Rosenberg (Water, Air, & Soil Pollution, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Needle biopsy of liver in a marine teleost, Pagrus auratus (Bloch & Schneider) - A.R. Dyer; P. De La M Hall; G.I. Matsumoto (Journal of Fish Diseases, 1997)

Comparison of two reagents, sodium pyrophosphate and sodium hydroxide, in the extraction of labile metal organic complexes - G. E. M. Hall; P. Pelchat (Water, Air, & Soil Pollution, 1997)

Comparison of two Reagents, Sodium Pyrophosphate and Sodium Hydroxide, in the Extraction of Labile Metal Organic Complexes - G.E.M. Hall; P. Pelchat (Water, Air, & Soil Pollution, 1997)

Fibromyalgia antirheumatic drug trials: Effects of a standardized instructional videotape on the reliability of observer-dependent outcome measures - N. Bellamy; R. Buchbinder; S. Hall; P. Lowthian; M. R. Patrick; P. F. J. Ryan; A. Stockman; G. Grant; S. Green; J. Campbell (Inflammopharmacology, 1997)

The influence of salinity on the chronic toxicity of atrazine to an estuarine copepod: Implications for development of an estuarine chronic criterion - L. W. Hall; M. C. Ziegenfuss; R. D. Anderson; D. P. Tierney (Archives of Environmental Contamination and Toxicology, 1995)

Human herpesvirus-6 strain groups: a nomenclature - D. Ablashi; H. Agut; Z. Berneman; G. Campadelli-Fiume; D. Carrigan; L. Ceccerini-Nelli; B. Chandran; S. Chou; H. Collandre; R. Cone; T. Dambaugh; S. Dewhurst; et al. (Archives of Virology, 1993)

Agressivite deConidiobolus obscurus via-a-vis du puceron du pois III. Activites enzymatiques exocellulaires - J. P. Latgé; L. Sampedro; R. Hall (BioControl, 1984)

Attempts to induce double resistance to drugs in the flagellate, Chilomonas paramecium - R. P. Hall (Archives of Microbiology, 1962)